Resin composition

A resin composition with specific solvent and filler ratios and viscosity range addresses nozzle clogging and resin separation issues, ensuring uniform film formation and improved insulation resistance in the slit coating method.

JP2025009980AActive Publication Date: 2025-01-20AJINOMOTO CO INC
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2024103185
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-28
Filing Date
2024-06-26
Publication Date
2025-01-20
Estimated Expiration
2044-06-26

AI Technical Summary

Technical Problem

Nozzle clogging and poor resin separation occur in the slit coating method due to solvent drying and viscosity issues, especially when using resins with low boiling point solvents, while high boiling point solvents lead to poor resin solubility and film thickness uniformity problems.

Method used

A resin composition comprising an epoxy resin, organic solvent with a boiling point below 100°C at 5-60% by mass, aromatic solvent at 35-60% by mass, and inorganic filler, with a viscosity of 3-5,000 mPa·s, is used to prevent nozzle clogging and ensure uniform film formation.

Benefits of technology

The resin composition effectively prevents nozzle clogging, resin separation, and achieves excellent thin film forming properties with uniform thickness, enhancing coating quality and insulation resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025009980000001
    Figure 2025009980000001
Patent Text Reader

Abstract

To provide a resin composition which can suppress resin separation failures accompanied by low dissolubility of a resin, can suppress clogging of a nozzle by dryness of the nozzle, on the other hand, can suppress cissing failures after coating, and is excellent in thin film formability.SOLUTION: A resin composition contains (A) an epoxy resin, (B) an organic solvent and (C) an inorganic filler, wherein when the total component (B) is 100 mass%, a percentage content of the organic solvent having a boiling point of lower than 100°C in the component (B) is 5 mass% or more and 60 mass% or less, when the total component (B) is 100 mass%, a percentage content of an aromatic solvent in the component (B) is 35 mass% or more, and viscosity measured by an E type viscometer under the conditions of 25°C and 50 rpm is 3 mPa s to 5,000 mPa s.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition containing an epoxy resin. [Background technology]

[0002] A known manufacturing technique for printed wiring boards is a build-up method in which insulating layers and conductor layers are alternately stacked. In the build-up method, the insulating layers are generally formed by curing a resin composition.

[0003] There are various known methods for forming an insulating layer, among which the slit coating method has several advantages.

[0004] For example, the slit coating method is advantageous in terms of cost reduction because it can be applied with a small amount of coating liquid. The amount of coating liquid required for the slit coating method is about 1 / 5 to 1 / 10 compared to, for example, the spin coating method. In addition, there is no particular restriction on the slit nozzle used for application, and any nozzle commercially available from multiple manufacturers can be used.

[0005] Furthermore, with the curtain coating method, the viscosity of the coating liquid changes when it comes into contact with the air, causing the solvent to evaporate, which changes the thickness of the film that is formed. However, with the slit coating method, the system is closed until the coating liquid is ejected from the nozzle, so there is no change in viscosity and a uniform film thickness can be formed.

[0006] In addition, the lamination method has the problem of resin seeping out, the spin coating method requires cleaning of the edges of the substrate (wafer) because the resin covers the edges, and the curtain coating method has the problem of the coating liquid seeping into the cross section of the substrate. On the other hand, the slit coating method can control the coating width, so seeping out does not occur and it is possible not to coat the edges. It is also possible to coat the edges of the substrate without the coating liquid seeping into the cross section. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 6658514 [Patent Document 2] Patent Publication No. 2021-157085 [Patent Document 3] JP 2020-050854 A [Patent Document 4] Patent No. 6844636 Summary of the Invention [Problem to be solved by the invention]

[0008] When forming an insulating layer by applying a resin composition, clogging of the nozzle of an application device such as a slit coater due to drying of the nozzle becomes an issue. In particular, clogging tends to occur easily when the boiling point of the solvent used is low. Conversely, when the boiling point of the solvent used is high, clogging of the nozzle can be suppressed, but the solubility of the resin is low, which may cause poor resin separation, and the drying property after application is also poor.

[0009] In addition, when using a resin composition containing an inorganic filler, adjusting the viscosity becomes an issue. For example, when the viscosity is high, it becomes difficult to eject the resin from a slit, and the uniformity of the film thickness also deteriorates, so that the thin film formability tends to decrease. On the other hand, when the viscosity is low, there is a concern that repelling defects may occur.

[0010] An object of the present invention is to provide a resin composition that can suppress resin separation failure due to low solubility of the resin, can suppress nozzle clogging due to drying of the nozzle, can suppress cissing failure after application, and has excellent thin film formability. [Means for solving the problem]

[0011] In order to achieve the objects of the present invention, the present inventors have thoroughly investigated solvents, viscosity, and the like, and as a result have unexpectedly found that a resin composition comprising (A) an epoxy resin, (B) an organic solvent, and (C) an inorganic filler, wherein the content of organic solvents having a boiling point of less than 100°C in component (B) is 5% by mass to 60% by mass when the total of component (B) is taken as 100% by mass, the content of aromatic solvents in component (B) is 35% by mass or more when the total of component (B) is taken as 100% by mass, and the resin composition has a viscosity of 3 mPa·s to 5,000 mPa·s as measured with an E-type viscometer under conditions of 25°C and 50 rpm, can suppress resin separation failures due to low solubility of the resin, can suppress nozzle clogging due to nozzle drying, can suppress cissing failures after application, and has excellent thin film formability, which has led to the completion of the present invention.

[0012] That is, the present invention includes the following. [1] A resin composition comprising (A) an epoxy resin, (B) an organic solvent, and (C) an inorganic filler, The content of the organic solvent having a boiling point of less than 100°C in the component (B) is 5% by mass to 60% by mass, relative to 100% by mass of the total of the component (B); the content of the aromatic solvent in the component (B) is 35% by mass or more, where the total amount of the component (B) is 100% by mass; The viscosity measured with an E-type viscometer at 25°C and 50 rpm is 3 mPa·s to 5,000 mPa·s. A resin composition for forming an insulating layer by applying the resin composition to a substrate by roll coating, spray coating, spin coating, bar coating, slit coating, curtain coating, or dipping to form a coating film, and then thermally curing the coating film. [2] The resin composition according to the above [1], which is a resin composition for forming an insulating layer by applying the resin composition to a substrate by a slit coating method to form a coating film and then thermally curing the coating film. [3] The resin composition according to the above [1], wherein the content of the (C) component is 85 mass% or less, when the total of the components other than the (B) component in the resin composition is 100 mass%. [4] The resin composition according to the above [1], wherein the content of the (C) component is 60 mass% or more, when the total of the components other than the (B) component in the resin composition is 100 mass%. [5] The resin composition according to the above [1], wherein the content of the aromatic solvent in the component (B) is 85 mass% or less, when the total amount of the component (B) is 100 mass%. [6] The resin composition according to the above [1], wherein the content of the organic solvent having a boiling point of 130°C or higher in the component (B) is 25% by mass to 90% by mass, relative to 100% by mass of the entire component (B). [7] The resin composition according to the above [1], wherein the content of the organic solvent having a boiling point of 100°C or higher and lower than 130°C in the component (B) is 1% by mass to 20% by mass, relative to 100% by mass of the entire component (B). [8] The resin composition according to the above [1], wherein the content of the organic solvent having a boiling point of 100°C or more and less than 130°C in the (B) component is 5% by mass or more, when the total (B) component is 100% by mass. [9] The resin composition according to the above [1], wherein the content of non-aromatic solvents having a boiling point of 130°C or higher in component (B) is 10% by mass or less, when the total amount of component (B) is 100% by mass.

[10] The resin composition according to the above [1], wherein the content of aromatic solvents having a boiling point of 130°C or higher in component (B) is 20% by mass or more, when the total amount of component (B) is 100% by mass.

[11] The resin composition according to [1] above, wherein the content of aromatic solvents having a boiling point of 130°C or higher in the aromatic solvent is 60% by mass or more, when the total aromatic solvents are 100% by mass.

[12] (B) component is C 9 Aromatic Hydrocarbons and C 10 The resin composition according to the above [1], further comprising an aromatic solvent selected from aromatic hydrocarbons.

[13] The resin composition according to the above [1], wherein the content of the organic solvent consisting of constituent atoms selected from carbon atoms, oxygen atoms, and hydrogen atoms in the (B) organic solvent is 98 mass% or more, when the total amount of the (B) component is 100 mass%.

[14] The resin composition according to the above [1], wherein the content of the (B) component is 15% by mass to 50% by mass, where the total amount of all components in the resin composition is 100% by mass.

[15] The resin composition according to the above [1], wherein the content of the radical polymerizable compound is 0% by mass to 2% by mass, relative to 100% by mass of the total of components other than the component (B) in the resin composition.

[16] The resin composition according to the above [1], having a viscosity of 50 mPa·s to 1,500 mPa·s as measured with an E-type viscometer at 25°C and 50 rpm.

[17] The resin composition according to the above item [1], having a thixotropy ratio, calculated by dividing the viscosity measured using an E-type viscometer at 25°C and 5 rpm by the viscosity measured using an E-type viscometer at 25°C and 50 rpm, of 1.00 to 1.50.

[18] The resin composition according to the above [1], having a thixotropy ratio, calculated by dividing the viscosity measured using an E-type viscometer at 25°C and 5 rpm by the viscosity measured using an E-type viscometer at 25°C and 50 rpm, of 1.00 to 1.15.

[19] A printed wiring board comprising an insulating layer made of a cured product of the resin composition according to any one of [1] to

[18] above.

[20] A semiconductor device comprising the printed wiring board described in

[19] above.

[21] A composition comprising: (A) an epoxy resin; (B) an organic solvent; and (C) an inorganic filler; The content of the organic solvent having a boiling point of less than 100°C in the component (B) is 5% by mass to 60% by mass, relative to 100% by mass of the total of the component (B); the content of the aromatic solvent in the component (B) is 35% by mass or more, where the total amount of the component (B) is 100% by mass; A method for producing a printed wiring board using a resin composition having a viscosity of 3 mPa·s to 5,000 mPa·s as measured with an E-type viscometer under conditions of 25°C and 50 rpm, A method for producing a printed wiring board, comprising the following steps (1) to (3): (1) A step of applying the resin composition onto a substrate by a slit coating method to form a coating film. (2) A step of vacuum drying the coating film and / or drying at a temperature of 50°C or higher but lower than 150°C. (3) A process of thermally curing the coating at a temperature of 150°C to 240°C to form an insulating layer. Effect of the Invention

[0013] According to the present invention, it is possible to provide a resin composition that can suppress resin separation failure due to low solubility of the resin, suppress nozzle clogging due to drying of the nozzle, and suppress repelling failure after application, and has excellent thin film formability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] The present invention will be described in detail below with reference to preferred embodiments. However, the present invention is not limited to the following embodiments and examples, and can be modified and implemented as desired without departing from the scope of the claims of the present invention and their equivalents.

[0015] The resin composition of the present invention is a resin composition for forming an insulating layer by applying the resin composition to a substrate by a roll coating method, a spray coating method, a spin coating method, a bar coating method, a slit coating method, a curtain coating method, or a dipping method (among which, the slit coating method is preferable) to form a coating film, and then thermally curing the coating film.

[0016] The resin composition of the present invention comprises (A) an epoxy resin, (B) an organic solvent, and (C) an inorganic filler, and the content of the organic solvent having a boiling point of less than 100°C in component (B) is 5% to 60% by mass when the total of component (B) is taken as 100% by mass, the content of the aromatic solvent in component (B) is 35% by mass or more when the total of component (B) is taken as 100% by mass, and the viscosity measured with an E-type viscometer under conditions of 25°C and 50 rpm is 3 mPa·s to 5,000 mPa·s. Such a resin composition can suppress resin separation failure due to low solubility of the resin and can suppress nozzle clogging due to nozzle drying, while suppressing cissing failure after application, and has excellent thin film formability.

[0017] The resin composition of the present invention may further contain (D) a curing agent, (E) a thermoplastic resin, (F) a curing accelerator, and (G) other additives in addition to (A) an epoxy resin, (B) an organic solvent, and (C) an inorganic filler. Each component contained in the resin composition of the present invention will be described in detail below.

[0018] <(A) Epoxy resin> The resin composition of the present invention contains (A) an epoxy resin. (A) The epoxy resin is a curable resin having an epoxy group.

[0019] Examples of the epoxy resin (A) include bixylenol type epoxy resins, bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bisphenol AF type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol novolac type epoxy resins, phenol novolac type epoxy resins, tert-butyl-catechol type epoxy resins, naphthalene type epoxy resins, naphthol type epoxy resins, anthracene type epoxy resins, glycidylamine type epoxy resins, glycidyl ester type epoxy resins, cresol novolac type epoxy resins, phenol aralkyl type epoxy resins, biphenyl type epoxy resins, linear aliphatic epoxy resins, epoxy resins having a butadiene structure, alicyclic epoxy resins, heterocyclic epoxy resins, spiro ring-containing epoxy resins, cyclohexane type epoxy resins, cyclohexane dimethanol type epoxy resins, naphthylene ether type epoxy resins, trimethylol type epoxy resins, tetraphenylethane type epoxy resins, isocyanurate type epoxy resins, and phenolphthalimidine type epoxy resins. The (A) epoxy resin may be used alone or in combination of two or more kinds.

[0020] The resin composition of the present invention preferably contains, as the epoxy resin (A), an epoxy resin having two or more epoxy groups in one molecule. The proportion of the epoxy resin having two or more epoxy groups in one molecule relative to 100 mass% of the epoxy resin (A) is preferably 50 mass% or more, more preferably 60 mass% or more, and particularly preferably 70 mass% or more.

[0021] Epoxy resins include epoxy resins that are liquid at a temperature of 20° C. (hereinafter sometimes referred to as "liquid epoxy resins") and epoxy resins that are solid at a temperature of 20° C. (hereinafter sometimes referred to as "solid epoxy resins"). The resin composition of the present invention may contain only a liquid epoxy resin as the epoxy resin, or may contain only a solid epoxy resin, or may contain both a liquid epoxy resin and a solid epoxy resin, but it is preferable that the resin composition contains both a liquid epoxy resin and a solid epoxy resin.

[0022] The liquid epoxy resin is preferably a liquid epoxy resin having two or more epoxy groups in one molecule.

[0023] As the liquid epoxy resin, glycirol type epoxy resin, bisphenol A type epoxy resin, bisphenol F type epoxy resin, bisphenol AF type epoxy resin, naphthalene type epoxy resin, glycidyl ester type epoxy resin, glycidyl amine type epoxy resin, phenol novolac type epoxy resin, alicyclic epoxy resin having an ester skeleton, cyclohexane dimethanol type epoxy resin, cyclic aliphatic glycidyl ether, and epoxy resin having a butadiene structure are preferred.

[0024] Specific examples of liquid epoxy resins include "EX-992L" manufactured by Nagase ChemteX Corporation, "YX7400" manufactured by Mitsubishi Chemical Corporation, "HP4032", "HP4032D", and "HP4032SS" manufactured by DIC Corporation (naphthalene type epoxy resins); "828US", "828EL", "825", and "Epikote 828EL" manufactured by Mitsubishi Chemical Corporation (bisphenol A type epoxy resins); and "jER807" and "1750" manufactured by Mitsubishi Chemical Corporation (bisphenol F type epoxy resins). epoxy resin); "jER152" (phenol novolac type epoxy resin) manufactured by Mitsubishi Chemical; "630", "630LSD", "604" (glycidylamine type epoxy resin) manufactured by Mitsubishi Chemical; "ED-523T" (glycirol type epoxy resin) manufactured by ADEKA; "EP-3950L", "EP-3980S" (glycidylamine type epoxy resin) manufactured by ADEKA; "EP-4088S" (dicyclopentadiene type epoxy resin) manufactured by ADEKA; "ZX1059" (mixture of bisphenol A type epoxy resin and bisphenol F type epoxy resin) manufactured by Nippon Steel Chemical & Material; "EX-721" (glycidyl ester type epoxy resin) manufactured by Nagase ChemteX; "EX-991L" (alkyleneoxy skeleton and butadiene skeleton-containing epoxy resin) manufactured by Nagase ChemteX; "Celloxide 2021P" (alicyclic epoxy resin with ester skeleton) manufactured by Daicel Corporation Examples of epoxy resins include "PB-3600" manufactured by Nippon Soda Co., Ltd., "JP-100", "JP-200", and "JP-400" (epoxy resins having a butadiene structure); "ZX1658" and "ZX1658GS" (liquid 1,4-glycidylcyclohexane type epoxy resins) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "EG-280" (fluorene structure-containing epoxy resin) manufactured by Osaka Gas Chemicals Co., Ltd.; and "EX-201" (cyclic aliphatic glycidyl ether) manufactured by Nagase ChemteX Corporation.

[0025] As the solid epoxy resin, a solid epoxy resin having three or more epoxy groups in one molecule is preferable, and an aromatic solid epoxy resin having three or more epoxy groups in one molecule is more preferable.

[0026] Preferred solid epoxy resins include bixylenol type epoxy resins, naphthalene type epoxy resins, naphthalene type tetrafunctional epoxy resins, naphthol novolac type epoxy resins, cresol novolac type epoxy resins, dicyclopentadiene type epoxy resins, trisphenol type epoxy resins, naphthol type epoxy resins, biphenyl type epoxy resins, naphthylene ether type epoxy resins, anthracene type epoxy resins, bisphenol A type epoxy resins, bisphenol AF type epoxy resins, phenol aralkyl type epoxy resins, tetraphenylethane type epoxy resins, and phenolphthalimidine type epoxy resins.

[0027] Specific examples of solid epoxy resins include "HP4032H" (naphthalene type epoxy resin) manufactured by DIC Corporation; "HP-4700" and "HP-4710" (naphthalene type tetrafunctional epoxy resins) manufactured by DIC Corporation; "N-690" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "N-695" (cresol novolac type epoxy resin) manufactured by DIC Corporation; "HP-7200", "HP-7200HH", "HP-7200H", and "HP-7200L" (dicyclopentadiene type epoxy resins) manufactured by DIC Corporation; "EXA-7311" and "E XA-7311-G3, EXA-7311-G4, EXA-7311-G4S, HP6000, HP6000L (naphthylene ether type epoxy resin); EPPN-502H (trisphenol type epoxy resin) manufactured by Nippon Kayaku; NC7000L (naphthol novolac type epoxy resin) manufactured by Nippon Kayaku; NC3000H, NC3000, NC3000L, NC3000FH, NC3100 (biphenyl type epoxy resin) manufactured by Nippon Steel Chemical & Material; ESN475V manufactured by Nippon Steel Chemical & Material; "ESN4100V" (naphthalene type epoxy resin); "ESN485" (naphthol type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "ESN375" (dihydroxynaphthalene type epoxy resin) manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YX4000H", "YX4000", "YX4000HK", "YL7890" (bixylenol type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YL6121" (biphenyl type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd.; "YX8800" (anthracene type epoxy resin) manufactured by Mitsubishi Chemical Co., Ltd. Examples of epoxy resins include "YX7700" (phenol aralkyl type epoxy resin); "PG-100" and "CG-500" manufactured by Osaka Gas Chemicals; "YX7760" (bisphenol AF type epoxy resin) manufactured by Mitsubishi Chemical; "YL7800" (fluorene type epoxy resin) manufactured by Mitsubishi Chemical; "jER1010" (bisphenol A type epoxy resin) manufactured by Mitsubishi Chemical; "jER1031S" (tetraphenylethane type epoxy resin) manufactured by Mitsubishi Chemical; and "WHR991S" (phenolphthalimidine type epoxy resin) manufactured by Nippon Kayaku Co., Ltd.These may be used alone or in combination of two or more.

[0028] When a solid epoxy resin and a liquid epoxy resin are used in combination as the (A) epoxy resin, the mass ratio thereof (solid epoxy resin:liquid epoxy resin) is preferably 50:1 to 1:10, more preferably 10:1 to 1:2, and particularly preferably 2:1 to 1:1.

[0029] The epoxy equivalent of the (A) epoxy resin is preferably 50 g / eq. to 5,000 g / eq., more preferably 60 g / eq. to 2,000 g / eq., even more preferably 70 g / eq. to 1,000 g / eq., and even more preferably 80 g / eq. to 500 g / eq. The epoxy equivalent is the mass of the resin per equivalent of epoxy group. This epoxy equivalent can be measured according to JIS K7236.

[0030] The weight average molecular weight (Mw) of the epoxy resin (A) is preferably from 100 to 5,000, more preferably from 250 to 3,000, and further preferably from 400 to 1500. The weight average molecular weight of the resin can be measured by gel permeation chromatography (GPC) as a polystyrene-equivalent value.

[0031] The content of the (A) epoxy resin in the resin composition is not particularly limited, but when the total of components other than the (B) organic solvent in the resin composition (non-volatile components) is taken as 100 mass%, it is preferably 50 mass% or less, more preferably 40 mass% or less, even more preferably 30 mass% or less, even more preferably 25 mass% or less, and particularly preferably 20 mass% or less; the lower limit is preferably 0.5 mass% or more, more preferably 1 mass% or more, even more preferably 5 mass% or more, even more preferably 10 mass% or more, and particularly preferably 15 mass% or more.

[0032] <(B) Organic solvent> The resin composition of the present invention contains an organic solvent (B). The organic solvent (B) described here is a liquid compound (a compound that is liquid at room temperature (25°C)) that is composed of skeletal atoms selected from carbon atoms and oxygen atoms and hydrogen atoms as non-skeletal atoms, and may further have an amide bond (>N-CO-), a urea bond (>N-CO-N<) or a cyano group (-CN) in addition to the skeletal atoms in the molecule, does not contain a carbon-carbon triple bond or a carbon-carbon double bond (except for bonds that constitute an aromatic ring), and has a boiling point of 250°C or less (preferably 220°C or less). In addition, the organic solvent (B) described here does not include those that correspond to the epoxy resin (A) or the curing agent (D). In this specification, the boiling point refers to the boiling point (i.e., the normal boiling point) under normal pressure (1 atm; 760 mmHg). The organic solvent (B) may be used alone or in combination of two or more kinds.

[0033] (B) The organic solvent includes aromatic and non-aromatic solvents.

[0034] Aromatic solvents are solvents that contain an aromatic ring in the molecule. Examples of aromatic solvents include C benzene (boiling point 80°C), toluene (boiling point 110°C), o-xylene (boiling point 144°C), m-xylene (boiling point 139°C), p-xylene (boiling point 138°C), and ethylbenzene (boiling point 136°C). 6-8 Aromatic hydrocarbons, 1,2,3-trimethylbenzene (boiling point 176°C), 1,3,5-trimethylbenzene (boiling point 165°C), 1,2,4-trimethylbenzene (boiling point 169°C), 4-ethyltoluene (boiling point 161°C), 3-ethyltoluene (boiling point 160°C), 2-ethyltoluene (boiling point 166°C), isopropylbenzene (boiling point 152°C), n-propylbenzene (boiling point 159°C), indane (boiling point 176°C), etc. 9Aromatic hydrocarbons, n-butylbenzene (boiling point 183°C), isobutylbenzene (boiling point 172°C), sec-butylbenzene (boiling point 173°C), tert-butylbenzene (boiling point 169°C), 1,2-diethylbenzene (boiling point 184°C), 1,3-diethylbenzene (boiling point 181°C), 1,4-diethylbenzene (boiling point 183°C), 3-ethyl-o-xylene (boiling point 194°C), 4-ethyl -o-xylene (boiling point 190°C), 2-ethyl-p-xylene (boiling point 187°C), 1-methyl-2-isopropylbenzene (boiling point 178°C), 1-methyl-3-isopropylbenzene (boiling point 175°C), 1-methyl-4-isopropylbenzene (boiling point 177°C), 1,2,3,5-tetramethylbenzene (boiling point 198°C), 1,2,3,4-tetrahydronaphthalene (boiling point 207°C), etc. 10 Aromatic hydrocarbons, such as 1,3-dimethyl-4-isopropylbenzene (boiling point 199°C) and 1-ethyl-4-isopropylbenzene (boiling point 197°C) 11 C such as aromatic hydrocarbons, 1,4-diisopropylbenzene (boiling point 210°C) 12 Examples of aromatic hydrocarbon-based solvents include aromatic hydrocarbons; aromatic ketone-based solvents such as acetophenone (boiling point 202°C); aromatic alcohol-based solvents such as benzyl alcohol (boiling point 205°C) and phenethyl alcohol (boiling point 219-221°C); aromatic ether-based solvents such as anisole (boiling point 154°C) and phenetole (boiling point 169°C); and aromatic ester-based solvents such as methyl benzoate (boiling point 198-200°C) and ethyl benzoate (boiling point 211-213°C).

[0035] The aromatic solvent preferably includes an aromatic hydrocarbon solvent. In one embodiment, the aromatic solvent is 6-8 More preferably, the aromatic solvent comprises an aromatic hydrocarbon, and particularly preferably, toluene. In one embodiment, the aromatic solvent comprises C 9 Aromatic Hydrocarbons and C 10 More preferably, the solvent contains an aromatic solvent selected from aromatic hydrocarbons.

[0036] As the aromatic solvent, commercially available aromatic mixed solvents may be used. Examples of commercially available aromatic mixed solvents include "IPZOL 100" (initial boiling point 159°C, dry point 172°C, aromatic content 99% or more) and "IPZOL 150" (initial boiling point 184°C, dry point 205°C, aromatic content 99% or more) manufactured by Idemitsu Kosan Co., Ltd., "Swasol 1000" (initial boiling point 163°C, dry point 175°C, aromatic content 100%) and "Swasol 1500" (initial boiling point 182°C, dry point 206°C, aromatic content 98%) manufactured by Maruzen Petrochemical Co., Ltd., "Solvent #100" (initial boiling point 150°C, dry point 185°C), and "Solvent #150" (initial boiling point 180°C, dry point 215°C) manufactured by Sankyo Chemical Co., Ltd.

[0037] A non-aromatic solvent is a solvent that does not contain an aromatic ring in the molecule. Examples of non-aromatic solvents include glycol-based solvents, glycol ether-based solvents, glycol ether ester-based solvents, aliphatic hydrocarbon-based solvents, aliphatic ketone-based solvents, aliphatic ester-based solvents, aliphatic ether-based solvents, aliphatic alcohol-based solvents, nitrile-based solvents, amide-based solvents, and urea-based solvents.

[0038] Examples of glycol-based solvents include ethylene glycol (boiling point 197° C.), diethylene glycol (boiling point 244° C.), propylene glycol (boiling point 188° C.), dipropylene glycol (boiling point 232° C.), and trimethylene glycol (boiling point 211-217° C.).

[0039] Examples of glycol ether-based solvents include cellosolves such as ethylene glycol monomethyl ether (also known as methyl cellosolve) (boiling point 124°C), ethylene glycol monoethyl ether (also known as cellosolve) (boiling point 135°C), ethylene glycol monopropyl ether (also known as propyl cellosolve) (boiling point 151°C), ethylene glycol monobutyl ether (also known as butyl cellosolve) (boiling point 171°C), ethylene glycol monoisobutyl ether (also known as isobutyl cellosolve) (boiling point 160°C), ethylene glycol mono-tert-butyl ether (also known as tert-butyl cellosolve) (boiling point 152°C), and ethylene glycol monohexyl ether (boiling point 208°C); diethylene glycol monomethyl ether (also known as methyl carbitol) (boiling point 193°C), diethylene glycol monoethyl ether (also known as carbitol) (boiling point 196°C), and the like. carbitols such as diethylene glycol monopropyl ether (also known as propyl carbitol) (boiling point 212-216°C), diethylene glycol monobutyl ether (DB) (also known as butyl carbitol) (boiling point 230°C); propylene glycol ethers such as propylene glycol monomethyl ether (PGM) (boiling point 120°C), propylene glycol monoethyl ether (boiling point 132°C), propylene glycol monopropyl ether (boiling point 150°C), and propylene glycol monobutyl ether (boiling point 170°C); dipropylene glycol ethers such as dipropylene glycol monomethyl ether (boiling point 188°C), dipropylene glycol monoethyl ether (boiling point 198°C), dipropylene glycol monopropyl ether (boiling point 210°C), and dipropylene glycol monobutyl ether (boiling point 215°C).

[0040] Examples of glycol ether ester solvents include cellosolve esters such as ethylene glycol monomethyl ether acetate (also known as methyl cellosolve acetate) (boiling point 145° C.), ethylene glycol monoethyl ether acetate (also known as cellosolve acetate) (boiling point 156° C.), and ethylene glycol monobutyl ether acetate (also known as butyl cellosolve acetate) (boiling point 191° C.); diethylene glycol monoethyl ether acetate (EDGAc) (also known as carbitol acetate) ( carbitol esters such as diethylene glycol monobutyl ether acetate (boiling point 217°C) and diethylene glycol monobutyl ether acetate (also known as butyl carbitol acetate) (boiling point 247°C); propylene glycol ether esters such as propylene glycol monomethyl ether acetate (PGMEA) (boiling point 146°C) and propylene glycol monoethyl ether acetate (boiling point 160°C); and dipropylene glycol ether esters such as dipropylene glycol monomethyl ether acetate (boiling point 200°C).

[0041] Examples of aliphatic hydrocarbon solvents include n-pentane (boiling point 36°C), n-hexane (boiling point 69°C), 2-methylpentane (also known as isohexane) (boiling point 60-62°C), n-heptane (boiling point 98°C), n-octane (boiling point 125°C), cyclopentane (boiling point 49°C), cyclohexane (boiling point 81°C), methylcyclohexane (boiling point 101°C), and ethylcyclohexane (boiling point 132°C).

[0042] Examples of aliphatic ketone solvents include aliphatic acyclic ketones such as acetone (boiling point 56°C), methyl ethyl ketone (MEK) (boiling point 79°C), diethyl ketone (boiling point 101°C), 2-pentanone (boiling point 101°C), methyl isobutyl ketone (boiling point 116°C), 2-hexanone (boiling point 127°C), 2-heptanone (MAK) (boiling point 151°C), and diisobutyl ketone (boiling point 168°C); and aliphatic cyclic ketones such as cyclopentanone (boiling point 131°C), cyclohexanone (boiling point 155°C), and 2-methylcyclohexanone (boiling point 162°C).

[0043] Aliphatic ester solvents are non-aromatic solvents having an ester structure that does not fall under the category of glycol ether ester solvents, and examples thereof include methyl acetate (boiling point 57°C), ethyl acetate (boiling point 77°C), n-propyl acetate (boiling point 96°C), isopropyl acetate (boiling point 89°C), n-butyl acetate (boiling point 126°C), isobutyl acetate (boiling point 118°C), sec-butyl acetate (boiling point 112°C), tert-butyl acetate (boiling point 97°C), n-pentyl acetate (boiling point 149°C), isopentyl acetate (boiling point 142°C), propyl acetate (boiling point 149 ... Examples of suitable hydroxyacid alkyl esters include methyl lactate (boiling point 144-145°C), ethyl lactate (boiling point 151-155°C), butyl lactate (boiling point 185-187°C), and other alkyl hydroxyacid esters; methyl acetoacetate (boiling point 170°C), ethyl acetoacetate (boiling point 184°C), and other alkyl ketoacid esters; and lactones such as γ-butyrolactone (GBL) (boiling point 204°C).

[0044] Aliphatic ether solvents are non-aromatic solvents having an ether structure that do not fall under the category of glycol ether solvents and glycol ether ester solvents, and examples of such solvents include aliphatic non-cyclic ethers such as diethyl ether (boiling point 34°C), diisopropyl ether (boiling point 68°C), and methyl tert-butyl ether (boiling point 55°C); and aliphatic cyclic ethers such as tetrahydrofuran (boiling point 66°C), 1,4-dioxane (boiling point 101°C), and 1,3-dioxolane (boiling point 75°C).

[0045] Aliphatic alcohol solvents are non-aromatic solvents having an alcohol structure that does not fall under glycol solvents and glycol ether solvents, and examples thereof include methanol (boiling point 64°C), ethanol (boiling point 78°C), n-propanol (boiling point 97°C), isopropanol (boiling point 82°C), n-butyl alcohol (boiling point 117°C), isobutyl alcohol (boiling point 108°C), sec-butyl alcohol (boiling point 99°C), tert-butyl alcohol (boiling point 82°C), n-pentyl alcohol (boiling point 138°C), isopentyl alcohol (boiling point 138°C), and butyl alcohol (boiling point 138°C). Examples of the alcohols include aliphatic acyclic alcohols such as alcohol (boiling point 131°C), sec-pentyl alcohol (boiling point 119°C), tert-pentyl alcohol (boiling point 102°C), neopentyl alcohol (boiling point 113°C), n-hexyl alcohol (boiling point 157°C), n-heptyl alcohol (boiling point 175°C), isoheptyl alcohol (boiling point 159°C), n-octyl alcohol (boiling point 195°C), and 2-ethylhexyl alcohol (boiling point 184°C); and aliphatic cyclic alcohols such as cyclohexanol (boiling point 161°C).

[0046] Examples of nitrile solvents include acetonitrile (boiling point: 82° C.) and propionitrile (boiling point: 97° C.).

[0047] Examples of amide solvents include non-cyclic amides such as N,N-dimethylformamide (DMF) (boiling point 153°C) and N,N-dimethylacetamide (DMA) (boiling point 165°C); and cyclic amides such as N-methyl-2-pyrrolidone (NMP) (boiling point 202°C).

[0048] Examples of urea-based solvents include acyclic ureas such as tetramethylurea (boiling point 176°C) and cyclic ureas such as 1,3-dimethyl-2-imidazolidinone (DMI) (boiling point 220°C) and N,N'-dimethylpropyleneurea (DMPU) (boiling point 246°C).

[0049] The non-aromatic solvent preferably includes a non-aromatic solvent selected from glycol ether solvents and aliphatic ketone solvents.

[0050] With respect to the content of organic solvents having a boiling point of less than 100°C in the (B) organic solvent, when the total (B) organic solvent contained in the resin composition is taken as 100 mass%, the lower limit is 5 mass% or more, preferably 8 mass% or more, more preferably 10 mass% or more, and particularly preferably 12 mass% or more, and the upper limit is 60 mass% or less, preferably 58 mass% or less, and more preferably 56 mass% or less.

[0051] With respect to the content of organic solvents having a boiling point of 130°C or more in the (B) organic solvent, when the total (B) organic solvent contained in the resin composition is taken as 100 mass%, the lower limit is preferably 1 mass% or more, more preferably 5 mass% or more, even more preferably 10 mass% or more, still more preferably 15 mass% or more, still more preferably 20 mass% or more, and particularly preferably 25 mass% or more, and the upper limit is 95 mass% or less, preferably 90 mass% or less, more preferably 85 mass% or less, and particularly preferably 80 mass% or less.

[0052] With respect to the content of organic solvents having a boiling point of 100°C or more and less than 130°C in the (B) organic solvent, when the total (B) organic solvent contained in the resin composition is taken as 100% by mass, the lower limit is 0% by mass or more, preferably 0.1% by mass or more, more preferably 0.5% by mass or more, even more preferably 1% by mass or more, even more preferably 3% by mass or more, and particularly preferably 5% by mass or more, and the upper limit is 95% by mass or less, preferably 70% by mass or less, more preferably 50% by mass or less, even more preferably 40% by mass or less, even more preferably 30% by mass or less, still more preferably 25% by mass or less, and particularly preferably 20% by mass or less.

[0053] With respect to the content of organic solvents having a boiling point of less than 75°C in the (B) organic solvent, when the total (B) organic solvent contained in the resin composition is taken as 100 mass%, the lower limit is 0 mass% or more and the upper limit is preferably 50 mass% or less, more preferably 30 mass% or less, even more preferably 10 mass% or less, still more preferably 5 mass% or less, even more preferably 1 mass% or less, and particularly preferably 0.1 mass% or less.

[0054] With respect to the content of the organic solvent having a boiling point of 220°C or more in the (B) organic solvent, when the total amount of the (B) organic solvent contained in the resin composition is taken as 100 mass%, the lower limit is 0 mass% or more and the upper limit is preferably 10 mass% or less, more preferably 5 mass% or less, even more preferably 1 mass% or less, and particularly preferably 0.1 mass% or less.

[0055] When the total amount of the (B) organic solvent contained in the resin composition is taken as 100 mass%, the content of the non-aromatic solvent in the (B) organic solvent has a lower limit of, for example, 0 mass% or more, preferably 1 mass% or more, more preferably 5 mass% or more, even more preferably 10 mass% or more, and particularly preferably 15 mass% or more, and an upper limit of 65 mass% or less.

[0056] With respect to the content of non-aromatic solvents having a boiling point of 130°C or more in the (B) organic solvent, when the total (B) organic solvent contained in the resin composition is taken as 100 mass%, the lower limit is, for example, 0 mass% or more, preferably 0.1 mass% or more, more preferably 1 mass% or more, even more preferably 1.5 mass% or more, particularly preferably 2 mass% or more, and most preferably 2.5 mass% or more, and the upper limit is 60 mass% or less, preferably 50 mass% or less, more preferably 40 mass% or less, even more preferably 30 mass% or less, even more preferably 20 mass% or less, and particularly preferably 10 mass% or less.

[0057] When the total amount of the (B) organic solvent contained in the resin composition is taken as 100 mass%, the aromatic solvent content in the (B) organic solvent has a lower limit of 35 mass% or more and an upper limit of, for example, 100 mass% or less, preferably 99 mass% or less, more preferably 95 mass% or less, even more preferably 90 mass% or less, particularly preferably 85 mass% or less, and most preferably 80 mass% or less.

[0058] With respect to the content of aromatic solvents having a boiling point of 130°C or more (preferably 160°C or more) in the (B) organic solvent, when the total (B) organic solvent contained in the resin composition is 100% by mass, the lower limit is, for example, 0% by mass or more, preferably 1% by mass or more, more preferably 5% by mass or more, even more preferably 10% by mass or more, even more preferably 15% by mass or more, and particularly preferably 20% by mass or more, and the upper limit is 95% by mass or less, preferably 90% by mass or less, more preferably 87% by mass or less, even more preferably 85% by mass or less, particularly preferably 83% by mass or less, and most preferably 80% by mass or less.

[0059] When the total aromatic solvents contained in the resin composition is taken as 100 mass%, the content of aromatic solvents having a boiling point of 130°C or higher (preferably 160°C or higher) in the aromatic solvent has a lower limit of, for example, 0 mass% or higher, preferably 1 mass% or higher, more preferably 10 mass% or higher, even more preferably 20 mass% or higher, still more preferably 30 mass% or higher, even more preferably 40 mass% or higher, particularly preferably 50 mass% or higher, and particularly preferably 60 mass% or higher, and an upper limit of 100 mass% or lower.

[0060] The content of the organic solvent selected from aromatic hydrocarbon solvents and aliphatic ketone solvents in the (B) organic solvent, relative to the total amount of the (B) organic solvents contained in the resin composition being 100 mass%, is preferably 50 mass% or more, more preferably 70 mass% or more, even more preferably 80 mass% or more, still more preferably 90 mass% or more, and particularly preferably 95 mass% or more.

[0061] The content of the organic solvent consisting of constituent atoms selected from carbon atoms, oxygen atoms, and hydrogen atoms (organic solvent not containing nitrogen atoms) in the (B) organic solvent, when the total amount of the (B) organic solvent contained in the resin composition is taken as 100 mass%, is preferably 60 mass% or more, more preferably 80 mass% or more, even more preferably 90 mass% or more, still more preferably 95 mass% or more, still more preferably 98 mass% or more, and particularly preferably 99 mass% or more.

[0062] With respect to the content of the (B) organic solvent in the resin composition, when all components in the resin composition are taken as 100 mass%, the lower limit is preferably 1 mass% or more, more preferably 5 mass% or more, even more preferably 10 mass% or more, still more preferably 13 mass% or more, even more preferably 15 mass% or more, and particularly preferably 17 mass% or more, and the upper limit is preferably 90 mass% or less, more preferably 70 mass% or less, even more preferably 60 mass% or less, even more preferably 55 mass% or less, and particularly preferably 50 mass% or less.

[0063] <(C) Inorganic filler> The resin composition of the present invention contains an inorganic filler (C). The inorganic filler (C) is contained in the resin composition in the form of particles.

[0064] (C) An inorganic compound is used as the material of the inorganic filler. (C) Examples of the material of the inorganic filler include silica, alumina, glass, cordierite, silicon oxide, barium sulfate, barium carbonate, talc, clay, mica powder, zinc oxide, hydrotalcite, boehmite, aluminum hydroxide, magnesium hydroxide, calcium carbonate, magnesium carbonate, magnesium oxide, boron nitride, aluminum nitride, manganese nitride, aluminum borate, strontium carbonate, strontium titanate, calcium titanate, magnesium titanate, bismuth titanate, titanium oxide, zirconium oxide, barium titanate, barium zirconate titanate, barium zirconate, calcium zirconate, zirconium phosphate, and zirconium tungstate phosphate. Among these, silica is particularly suitable. Examples of silica include amorphous silica, fused silica, crystalline silica, synthetic silica, and hollow silica. In addition, spherical silica is preferable as the silica. The (C) inorganic filler may be used alone or in combination of two or more kinds in any ratio.

[0065] Examples of commercially available (C) inorganic fillers include "SP60-05" and "SP507-05" manufactured by Nippon Steel Chemical & Material Co., Ltd.; "YC100C", "YA050C", "YA050C-MJE", "YA010C", "SC2500SQ", "SO-C4", "SO-C2", and "SO-C1" manufactured by Admatechs Co., Ltd.; "UFP-30", "DAW-03", and "FB-105FD" manufactured by Denka Co., Ltd.; "Silfil NSS-3N", "Silfil NSS-4N", and "Silfil NSS-5N" manufactured by Tokuyama Corporation; "Cellspheres" and "MGH-005" manufactured by Taiheiyo Cement Corporation; and "Sfereek" and "BA-1" manufactured by JGC Catalysts and Chemicals Co., Ltd.

[0066] The average particle size of the (C) inorganic filler is not particularly limited, but is preferably 10 μm or less, more preferably 5 μm or less, even more preferably 3 μm or less, even more preferably 2 μm or less, and particularly preferably 1 μm or less. The lower limit of the average particle size of the (C) inorganic filler is not particularly limited, but is preferably 0.01 μm or more, more preferably 0.05 μm or more, even more preferably 0.1 μm or more, and particularly preferably 0.2 μm or more. The average particle size of the (C) inorganic filler can be measured by a laser diffraction / scattering method based on the Mie scattering theory. Specifically, the particle size distribution of the inorganic filler is created on a volume basis using a laser diffraction / scattering type particle size distribution measuring device, and the median diameter is taken as the average particle size. The measurement sample can be prepared by weighing 100 mg of the inorganic filler and 10 g of methyl ethyl ketone into a vial and dispersing it by ultrasonic waves for 10 minutes. The measurement sample was measured using a laser diffraction type particle size distribution measuring device with blue and red light source wavelengths, and the particle size distribution of the inorganic filler on a volume basis was measured using a flow cell method, and the average particle size was calculated as the median diameter from the particle size distribution obtained. An example of a laser diffraction type particle size distribution measuring device is the "LA-960" manufactured by Horiba, Ltd.

[0067] The specific surface area of ​​the (C) inorganic filler is not particularly limited, but is preferably 0.1 m 2 / g or more, more preferably 0.5m 2 / g or more, more preferably 1m 2 / g or more, particularly preferably 3m 2 The upper limit of the specific surface area of ​​the inorganic filler (C) is not particularly limited, but is preferably 100 m 2 / g or less, more preferably 70m 2 / g or less, more preferably 50m 2 / g or less, and even more preferably 30m 2 / g or less, particularly preferably 10m 2 The specific surface area of ​​the inorganic filler is obtained by adsorbing nitrogen gas onto the surface of a sample using a specific surface area measuring device (Macsorb HM-1210 manufactured by Mountec Co., Ltd.) according to the BET method, and calculating the specific surface area using the BET multipoint method.

[0068] (C) The inorganic filler is preferably treated with a surface treatment agent from the viewpoint of improving moisture resistance and dispersibility. Examples of the surface treatment agent include a fluorine-containing silane coupling agent, an aminosilane coupling agent, an epoxysilane coupling agent, a mercaptosilane coupling agent, a silane coupling agent, an alkoxysilane, an organosilazane compound, and a titanate coupling agent. The surface treatment agent may be used alone or in any combination of two or more.

[0069] Examples of commercially available surface treatment agents include Shin-Etsu Chemical Co., Ltd.'s "KBM403" (3-glycidoxypropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM803" (3-mercaptopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBE903" (3-aminopropyltriethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM573" (N-phenyl-3-aminopropyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "SZ-31" (hexamethyldisilazane), Shin-Etsu Chemical Co., Ltd.'s "KBM103" (phenyltrimethoxysilane), Shin-Etsu Chemical Co., Ltd.'s "KBM-4803" (long-chain epoxy-type silane coupling agent), and Shin-Etsu Chemical Co., Ltd.'s "KBM-7103" (3,3,3-trifluoropropyltrimethoxysilane).

[0070] From the viewpoint of improving the dispersibility of the inorganic filler, the degree of surface treatment with the surface treatment agent is preferably within a predetermined range. Specifically, 100% by mass of the inorganic filler is preferably surface-treated with 0.2% to 5% by mass of the surface treatment agent, more preferably 0.2% to 3% by mass, and even more preferably 0.3% to 2% by mass.

[0071] The degree of surface treatment with the surface treatment agent can be evaluated by the amount of carbon per unit surface area of ​​the inorganic filler. From the viewpoint of improving the dispersibility of the inorganic filler, the amount of carbon per unit surface area of ​​the inorganic filler is 0.02 mg / m 2 More than 0.1 mg / m is preferable. 2 More preferably, 0.2 mg / m or more 2 On the other hand, from the viewpoint of preventing an increase in the melt viscosity of the resin composition, it is more preferable that the content is 1.0 mg / m 2 Less than 0.8 mg / m is preferred. 2 Less than 0.5 mg / m is more preferable. 2 The following is even more preferred:

[0072] (C) The amount of carbon per unit surface area of ​​the inorganic filler can be measured after the surface-treated inorganic filler is washed with a solvent (e.g., methyl ethyl ketone (MEK)). Specifically, a sufficient amount of MEK as a solvent is added to the inorganic filler that has been surface-treated with a surface treatment agent, and ultrasonic cleaning is performed at 25°C for 5 minutes. After removing the supernatant and drying the solid content, the amount of carbon per unit surface area of ​​the inorganic filler can be measured using a carbon analyzer. As the carbon analyzer, the "EMIA-320V" manufactured by Horiba, Ltd., or the like can be used.

[0073] When the total of components other than the (B) organic solvent in the resin composition (non-volatile components) is taken as 100 mass%, the upper limit of the content of the (C) inorganic filler in the resin composition is preferably 90 mass% or less, more preferably 85 mass% or less, even more preferably 80 mass% or less, and particularly preferably 78 mass% or less; and the lower limit is preferably 1 mass% or more, preferably 10 mass% or more, more preferably 30 mass% or more, even more preferably 40 mass% or more, even more preferably 50 mass% or more, still more preferably 60 mass% or more, and particularly preferably 70 mass% or more.

[0074] The mass ratio of the (C) inorganic filler to the (A) epoxy resin in the resin composition ((C) inorganic filler / (A) epoxy resin) is not particularly limited, but is preferably 1 or more, more preferably 2 or more, and particularly preferably 4 or more. The upper limit of the mass ratio is not particularly limited, but is preferably 20 or less, more preferably 10 or less, and particularly preferably 5 or less.

[0075] The total content of the (A) epoxy resin and the (C) inorganic filler in the resin composition is preferably 70 mass% or more, more preferably 80 mass% or more, even more preferably 85 mass% or more, and particularly preferably 90 mass% or more, when the total of the components other than the (B) organic solvent in the resin composition (non-volatile components) is taken as 100 mass%.

[0076] <(D) Hardener> The resin composition of the present invention may contain a curing agent (D) as an optional component. The curing agent (D) may be used alone or in any combination of two or more. The curing agent (D) may have a function of reacting with the epoxy resin (A) to cure it.

[0077] The (D) curing agent is not particularly limited, but examples thereof include active ester curing agents, phenolic curing agents, carbodiimide curing agents, acid anhydride curing agents, amine curing agents, benzoxazine curing agents, cyanate ester curing agents, and thiol curing agents. In one embodiment, the (D) curing agent is particularly preferably an active ester curing agent from the viewpoint of further reducing the dielectric tangent. In one embodiment, the (D) curing agent is particularly preferably a phenolic curing agent from the viewpoint of further improving the curability.

[0078] As the active ester curing agent, generally, compounds having two or more highly reactive ester groups in one molecule, such as phenol esters, thiophenol esters, N-hydroxyamine esters, and esters of heterocyclic hydroxy compounds, are preferably used. The active ester compound is preferably one obtained by a condensation reaction between a carboxylic acid compound and / or a thiocarboxylic acid compound and a hydroxy compound and / or a thiol compound. In particular, from the viewpoint of improving heat resistance, an active ester compound obtained from a carboxylic acid compound and a hydroxy compound is preferred, and an active ester compound obtained from a carboxylic acid compound and a phenol compound and / or a naphthol compound is more preferred. Examples of the carboxylic acid compound include benzoic acid, acetic acid, succinic acid, maleic acid, itaconic acid, phthalic acid, isophthalic acid, terephthalic acid, and pyromellitic acid. Examples of phenol compounds or naphthol compounds include hydroquinone, resorcin, bisphenol A, bisphenol F, bisphenol S, phenolphthaline, methylated bisphenol A, methylated bisphenol F, methylated bisphenol S, phenol, o-cresol, m-cresol, p-cresol, catechol, α-naphthol, β-naphthol, 1,5-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, dihydroxybenzophenone, trihydroxybenzophenone, tetrahydroxybenzophenone, phloroglucin, benzenetriol, dicyclopentadiene-type diphenol compounds, phenol novolac, etc. Here, the term "dicyclopentadiene-type diphenol compounds" refers to diphenol compounds obtained by condensing one molecule of dicyclopentadiene with two molecules of phenol.

[0079] Specifically, the active ester curing agent is preferably a dicyclopentadiene type active ester compound, a naphthalene type active ester compound containing a naphthalene structure, an active ester compound containing an acetylated product of phenol novolac, or an active ester compound containing a benzoylated product of phenol novolac, and more preferably at least one selected from a dicyclopentadiene type active ester compound and a naphthalene type active ester compound. As the dicyclopentadiene type active ester compound, an active ester compound containing a dicyclopentadiene type diphenol structure is preferable.

[0080] Commercially available active ester curing agents include active ester compounds containing a dicyclopentadiene-type diphenol structure, such as "EXB9451", "EXB9460", "EXB9460S", "HPC-8000L-65TM", "HPC-8000-65T", "HPC-8000H", and "HPC-8000H-65TM" (manufactured by DIC Corporation); and active ester compounds containing a naphthalene structure, such as "HP-B-8151-62T", "EXB-8100L-65T", "EXB-9416-70BK", and "HPC-8150-62T". and "EXB-8" (manufactured by DIC Corporation); an active ester compound containing phosphorus, "EXB9401" (manufactured by DIC Corporation), an active ester compound which is an acetylated product of phenol novolac, "DC808" (manufactured by Mitsubishi Chemical Corporation), active ester compounds which are benzoylated products of phenol novolac, "YLH1026", "YLH1030", and "YLH1048" (manufactured by Mitsubishi Chemical Corporation), and an active ester compound containing a styryl group and a naphthalene structure, "PC1300-02-65MA" (manufactured by Air Water Corporation), etc.

[0081] As the phenol-based curing agent, from the viewpoint of heat resistance and water resistance, a phenol-based curing agent having a novolac structure is preferable. Also, from the viewpoint of adhesion to the adherend, a nitrogen-containing phenol-based curing agent is preferable, and a triazine skeleton-containing phenol-based curing agent is more preferable. Among them, from the viewpoint of highly satisfying heat resistance, water resistance, and adhesion, a triazine skeleton-containing phenol novolac resin is preferable. Specific examples of phenol-based curing agents include "MEH-7700", "MEH-7810", and "MEH-7851" manufactured by Meiwa Kasei Co., Ltd.; "NHN", "CBN", and "GPH" manufactured by Nippon Kayaku Co., Ltd.; "SN-170", "SN-180", "SN-190", "SN-475", "SN-485", "SN-495", "SN-375", and "SN-395" manufactured by Nippon Steel Chemical & Material Co., Ltd.; and "LA-7052", "LA-7054", "LA-3018", "LA-3018-50P", "LA-1356", "TD2090", and "KA-1160" manufactured by DIC Corporation.

[0082] Examples of the carbodiimide-based curing agent include curing agents having one or more, preferably two or more, carbodiimide structures in one molecule, such as aliphatic biscarbodiimides, such as tetramethylene-bis(t-butylcarbodiimide) and cyclohexane bis(methylene-t-butylcarbodiimide); aromatic biscarbodiimides, such as phenylene-bis(xylylcarbodiimide); and aliphatic polycarbodiimides, such as polyhexamethylenecarbodiimide, polytrimethylhexamethylenecarbodiimide, polycyclohexylenecarbodiimide, poly(methylenebiscyclohexylenecarbodiimide), and poly(isophoronecarbodiimide). ; polycarbodiimides such as aromatic polycarbodiimides such as poly(phenylenecarbodiimide), poly(naphthylenecarbodiimide), poly(tolylenecarbodiimide), poly(methyldiisopropylphenylenecarbodiimide), poly(triethylphenylenecarbodiimide), poly(diethylphenylenecarbodiimide), poly(triisopropylphenylenecarbodiimide), poly(diisopropylphenylenecarbodiimide), poly(xylylenecarbodiimide), poly(tetramethylxylylenecarbodiimide), poly(methylenediphenylenecarbodiimide), and poly[methylenebis(methylphenylene)carbodiimide].

[0083] Commercially available carbodiimide curing agents include, for example, "Carbodilite V-02B", "Carbodilite V-03", "Carbodilite V-04K", "Carbodilite V-07", and "Carbodilite V-09" manufactured by Nisshinbo Chemical Inc.; and "Stavaxol P", "Stavaxol P400", and "Hi-Kasil 510" manufactured by Rhein Chemie.

[0084] Examples of the acid anhydride curing agent include a curing agent having one or more acid anhydride groups in one molecule, and a curing agent having two or more acid anhydride groups in one molecule is preferable. Specific examples of the acid anhydride curing agent include phthalic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, hydrogenated methylnadic anhydride, trialkyltetrahydrophthalic anhydride, dodecenyl succinic anhydride, 5-(2,5-dioxotetrahydro-3-furanyl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenonetetracarboxylic dianhydride, and the like. Examples of acid anhydrides include anhydrides, biphenyltetracarboxylic dianhydride, naphthalenetetracarboxylic dianhydride, oxydiphthalic dianhydride, 3,3'-4,4'-diphenylsulfonetetracarboxylic dianhydride, 1,3,3a,4,5,9b-hexahydro-5-(tetrahydro-2,5-dioxo-3-furanyl)-naphtho[1,2-C]furan-1,3-dione, ethylene glycol bis(anhydrotrimellitate), and polymeric acid anhydrides such as styrene-maleic acid resin, which is a copolymer of styrene and maleic acid. Commercially available acid anhydride curing agents include "HNA-100", "MH-700", "MTA-15", "DDSA", and "OSA" manufactured by New Japan Chemical Co., Ltd., "YH-306" and "YH-307" manufactured by Mitsubishi Chemical Corporation, "HN-2200" and "HN-5500" manufactured by Hitachi Chemical Co., Ltd., and "EF-30", "EF-40", "EF-60", and "EF-80" manufactured by Clay Valley.

[0085] The amine-based curing agent may be a curing agent having one or more, preferably two or more, amino groups in one molecule, such as aliphatic amines, polyether amines, alicyclic amines, aromatic amines, etc., and among them, aromatic amines are preferred from the viewpoint of achieving the desired effects of the present invention. The amine-based curing agent is preferably a primary amine or secondary amine, and more preferably a primary amine. Specific examples of amine-based curing agents include 4,4'-methylenebis(2,6-dimethylaniline), 4,4'-diaminodiphenylmethane, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, m-phenylenediamine, m-xylylenediamine, diethyltoluenediamine, 4,4'-diaminodiphenyl ether, 3,3'-dimethyl-4,4'-diaminobiphenyl, 2,2'-dimethyl-4,4'-diaminobiphenyl, 3,3'-dihydroxybenzidine, and 2,2-bis(3-amino-4-hydroxyphenyl)propane. propane, 3,3-dimethyl-5,5-diethyl-4,4-diphenylmethanediamine, 2,2-bis(4-aminophenyl)propane, 2,2-bis(4-(4-aminophenoxy)phenyl)propane, 1,3-bis(3-aminophenoxy)benzene, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 4,4'-bis(4-aminophenoxy)biphenyl, bis(4-(4-aminophenoxy)phenyl)sulfone, bis(4-(3-aminophenoxy)phenyl)sulfone, and the like. As the amine-based curing agent, commercially available products may be used, and examples thereof include "SEIKACURE-S" manufactured by Seika Corporation, "KAYABOND C-200S", "KAYABOND C-100", "KAYAHARD AA", "KAYAHARD AB", and "KAYAHARD AS" manufactured by Nippon Kayaku Co., Ltd., and "Epicure W" manufactured by Mitsubishi Chemical Corporation.

[0086] Specific examples of benzoxazine-based curing agents include "JBZ-OP100D" and "ODA-BOZ" manufactured by JFE Chemical Corporation; "HFB2006M" manufactured by Showa Polymer Co., Ltd.; and "Pd" and "Fa" manufactured by Shikoku Chemical Industry Co., Ltd.

[0087] Examples of the cyanate ester curing agent include bifunctional cyanate resins such as bisphenol A dicyanate, polyphenol cyanate (oligo(3-methylene-1,5-phenylene cyanate)), 4,4'-methylenebis(2,6-dimethylphenyl cyanate), 4,4'-ethylidene diphenyl dicyanate, hexafluorobisphenol A dicyanate, 2,2-bis(4-cyanate)phenylpropane, 1,1-bis(4-cyanate phenylmethane), bis(4-cyanate-3,5-dimethylphenyl)methane, 1,3-bis(4-cyanate phenyl-1-(methylethylidene))benzene, bis(4-cyanate phenyl)thioether, and bis(4-cyanate phenyl)ether; polyfunctional cyanate resins derived from phenol novolac and cresol novolac; and prepolymers in which these cyanate resins are partially converted to triazine. Specific examples of cyanate ester-based curing agents include "PT30" and "PT60" (both of which are phenol novolac-type multifunctional cyanate ester resins), "BA230" and "BA230S75" (prepolymers in which part or all of bisphenol A dicyanate has been converted to triazine to form a trimer), all of which are manufactured by Lonza Japan.

[0088] Examples of thiol-based curing agents include trimethylolpropane tris(3-mercaptopropionate), pentaerythritol tetrakis(3-mercaptobutyrate), and tris(3-mercaptopropyl)isocyanurate.

[0089] The reactive group equivalent of the (D) curing agent is preferably 50 g / eq. to 3000 g / eq., more preferably 100 g / eq. to 1000 g / eq., further preferably 100 g / eq. to 500 g / eq., and particularly preferably 100 g / eq. to 300 g / eq. The reactive group equivalent is the mass of the (D) curing agent per equivalent of reactive group.

[0090] When a phenol-based curing agent is included as the (D) curing agent, the content of the phenol-based curing agent in the resin composition is preferably 0.5 mass% or more from the viewpoint of further improving the curability, and is preferably 5 mass% or less, more preferably 3 mass% or less, from the viewpoint of keeping the dielectric tangent low, where the total of the components other than the (B) organic solvent in the resin composition (non-volatile components) is taken as 100 mass%.

[0091] When an active ester curing agent is included as the (D) curing agent, the content of the active ester curing agent in the resin composition is preferably 0.1% by mass or more, more preferably 1% by mass or more, even more preferably 3% by mass or more, and particularly preferably 5% by mass or more, from the viewpoint of suppressing the dielectric tangent lower, when the total (non-volatile components) of the components other than the (B) organic solvent in the resin composition is taken as 100% by mass. In addition, the content of the active ester curing agent in the resin composition is preferably 10% by mass or more, more preferably 30% by mass or more, even more preferably 40% by mass or more, and particularly preferably 50% by mass or more, from the viewpoint of suppressing the dielectric tangent lower, when the (D) curing agent in the resin composition is taken as 100% by mass.

[0092] The content of the (D) curing agent in the resin composition is not particularly limited, but when the total of the components other than the (B) organic solvent in the resin composition (non-volatile components) is taken as 100 mass%, it is preferably 30 mass% or less, more preferably 20 mass% or less, even more preferably 15 mass% or less, and particularly preferably 10 mass% or less, and the lower limit may be 0 mass% or more, 0.01 mass% or more, or 0.1 mass% or more, preferably 1 mass% or more, more preferably 3 mass% or more, and particularly preferably 5 mass% or more.

[0093] The mass ratio of the (D) curing agent to the (A) epoxy resin in the resin composition ((D) curing agent / (A) epoxy resin) is not particularly limited, but is preferably 0.02 or more, more preferably 0.05 or more, and particularly preferably 0.2 or more. The upper limit of the mass ratio is not particularly limited, but is preferably 2 or less, more preferably 1 or less, and particularly preferably 0.5 or less.

[0094] The total content of the (A) epoxy resin, (C) inorganic filler, and (D) curing agent in the resin composition is preferably 80 mass% or more, more preferably 90 mass% or more, even more preferably 95 mass% or more, and particularly preferably 98 mass% or more, when the total of the components other than the (B) organic solvent in the resin composition (non-volatile components) is taken as 100 mass%.

[0095] <(E) Thermoplastic resin> The resin composition of the present invention may further contain a thermoplastic resin (E) as an optional component. The thermoplastic resin (E) described here is a component other than the epoxy resin (A) and the curing agent (D) described above.

[0096] Examples of the (E) thermoplastic resin include polyimide resin, phenoxy resin, polyvinyl acetal resin, polyolefin resin, polybutadiene resin, polyamideimide resin, polyetherimide resin, polysulfone resin, polyethersulfone resin, polyphenylene ether resin, polycarbonate resin, polyetheretherketone resin, polyester resin, etc. In one embodiment, the (E) thermoplastic resin preferably contains a thermoplastic resin selected from the group consisting of polyimide resin and phenoxy resin, more preferably contains phenoxy resin. Moreover, the thermoplastic resin may be used alone or in combination of two or more kinds.

[0097] Specific examples of polyimide resins include "SLK-6100" manufactured by Shin-Etsu Chemical Co., Ltd., and "Rikacoat SN20" and "Rikacoat PN20" manufactured by New Japan Chemical Co., Ltd.

[0098] Examples of the phenoxy resin include phenoxy resins having one or more skeletons selected from the group consisting of bisphenol A skeleton, bisphenol F skeleton, bisphenol S skeleton, bisphenolacetophenone skeleton, novolac skeleton, biphenyl skeleton, fluorene skeleton, dicyclopentadiene skeleton, norbornene skeleton, naphthalene skeleton, anthracene skeleton, adamantane skeleton, terpene skeleton, and trimethylcyclohexane skeleton. The terminal of the phenoxy resin may be any functional group such as a phenolic hydroxyl group or an epoxy group.

[0099] Specific examples of phenoxy resins include "1256" and "4250" manufactured by Mitsubishi Chemical Corporation (both of which are phenoxy resins containing a bisphenol A skeleton); "YX8100" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol S skeleton); "YX6954" manufactured by Mitsubishi Chemical Corporation (phenoxy resin containing a bisphenol acetophenone skeleton), "FX280" and "FX293" manufactured by Nippon Steel Chemical & Material Co., Ltd.; and "YX7200B35", "YL7500BH30", "YX6954BH30", "YX7553BH30", "YL7769BH30", "YL6794", "YL7213", "YL7290", and "YL7482" manufactured by Mitsubishi Chemical Corporation.

[0100] Examples of polyvinyl acetal resin include polyvinyl formal resin and polyvinyl butyral resin, and polyvinyl butyral resin is preferred.Specific examples of polyvinyl acetal resin include "Denka Butyral 4000-2", "Denka Butyral 5000-A", "Denka Butyral 6000-C", and "Denka Butyral 6000-EP" manufactured by Denki Kagaku Kogyo Co., Ltd.; S-LEC BH series, BX series (e.g. BX-5Z), KS series (e.g. KS-1), BL series, and BM series manufactured by Sekisui Chemical Co., Ltd.

[0101] Examples of polyolefin resins include ethylene-based copolymer resins such as low-density polyethylene, very low-density polyethylene, high-density polyethylene, ethylene-vinyl acetate copolymer, ethylene-ethyl acrylate copolymer, and ethylene-methyl acrylate copolymer; and polyolefin polymers such as polypropylene and ethylene-propylene block copolymer.

[0102] Examples of polybutadiene resins include hydrogenated polybutadiene skeleton-containing resins, hydroxy group-containing polybutadiene resins, phenolic hydroxy group-containing polybutadiene resins, carboxy group-containing polybutadiene resins, acid anhydride group-containing polybutadiene resins, epoxy group-containing polybutadiene resins, isocyanate group-containing polybutadiene resins, urethane group-containing polybutadiene resins, polyphenylene ether-polybutadiene resins, and the like.

[0103] Specific examples of polyamide-imide resins include "Viromax HR11NN" and "Viromax HR16NN" manufactured by Toyobo Co., Ltd. Specific examples of polyamide-imide resins also include modified polyamide-imides such as "KS9100" and "KS9300" (polysiloxane skeleton-containing polyamide-imide) manufactured by Hitachi Chemical Co., Ltd.

[0104] A specific example of the polyethersulfone resin is "PES5003P" manufactured by Sumitomo Chemical Co., Ltd.

[0105] Specific examples of polysulfone resins include polysulfones "P1700" and "P3500" manufactured by Solvay Advanced Polymers.

[0106] A specific example of the polyphenylene ether resin is NORYL SA90 manufactured by SABIC, etc. A specific example of the polyetherimide resin is ULTEM manufactured by GE, etc.

[0107] Examples of polycarbonate resins include hydroxyl group-containing carbonate resins, phenolic hydroxyl group-containing carbonate resins, carboxyl group-containing carbonate resins, acid anhydride group-containing carbonate resins, isocyanate group-containing carbonate resins, and urethane group-containing carbonate resins. Specific examples of polycarbonate resins include Mitsubishi Gas Chemical's "FPC0220," Asahi Kasei Chemical's "T6002" and "T6001" (polycarbonate diols), and Kuraray's "C-1090," "C-2090," and "C-3090" (polycarbonate diols). Specific examples of polyether ether ketone resins include Sumitomo Chemical's "Sumiploy K."

[0108] Examples of the polyester resin include polyethylene terephthalate resin, polyethylene naphthalate resin, polybutylene terephthalate resin, polybutylene naphthalate resin, polytrimethylene terephthalate resin, polytrimethylene naphthalate resin, and polycyclohexane dimethyl terephthalate resin.

[0109] The weight average molecular weight (Mw) of the (E) thermoplastic resin is, from the viewpoint of significantly obtaining the effects of the present invention, preferably 5,000 or more, more preferably 8,000 or more, even more preferably 10,000 or more, particularly preferably 20,000 or more, and is preferably 100,000 or less, more preferably 70,000 or less, even more preferably 60,000 or less, particularly preferably 50,000 or less.

[0110] The content of the (E) thermoplastic resin in the resin composition is not particularly limited, but from the viewpoint of significantly obtaining the desired effects of the present invention, when the total of the components other than the (B) organic solvent in the resin composition (non-volatile components) is taken as 100 mass%, the content is preferably 20 mass% or less, more preferably 10 mass% or less, even more preferably 5 mass% or less, even more preferably 3 mass% or less, and particularly preferably 2 mass% or less, and the lower limit can be, for example, 0 mass% or more, 0.01 mass% or more, 0.1 mass% or more, 0.5 mass% or more, 1 mass% or more, etc.

[0111] The mass ratio of the thermoplastic resin (E) to the epoxy resin (A) in the resin composition (thermoplastic resin (E) / epoxy resin (A)) is not particularly limited, but is, for example, 0 or more, preferably 0.01 or more, more preferably 0.03 or more, and particularly preferably 0.05 or more. The upper limit is not particularly limited, but is preferably 1 or less, more preferably 0.5 or less, and particularly preferably 0.2 or less.

[0112] <(F) Curing accelerator> The resin composition of the present invention may contain, as an optional component, a curing accelerator (F), which functions as a curing catalyst for accelerating the curing of the epoxy resin (A).

[0113] Examples of the (F) curing accelerator include phosphorus-based curing accelerators, urea-based curing accelerators, guanidine-based curing accelerators, imidazole-based curing accelerators, metal-based curing accelerators, and amine-based curing accelerators. The (F) curing accelerator preferably contains a curing accelerator selected from imidazole-based curing accelerators and amine-based curing accelerators. The (F) curing accelerator may be used alone or in combination of two or more.

[0114] Examples of the phosphorus-based curing accelerator include aliphatic phosphonium salts such as tetrabutylphosphonium bromide, tetrabutylphosphonium chloride, tetrabutylphosphonium acetate, tetrabutylphosphonium decanoate, tetrabutylphosphonium laurate, bis(tetrabutylphosphonium)pyromellitate, tetrabutylphosphonium hydrogenhexahydrophthalate, tetrabutylphosphonium 2,6-bis[(2-hydroxy-5-methylphenyl)methyl]-4-methylphenolate, and di-tert-butylmethylphosphonium tetraphenylborate; methyltriphenylphosphonium bromide, ethyltriphenylphosphonium bromide, propyltriphenylphosphonium bromide, butyltriphenylphosphonium bromide, benzyltriphenylphosphonium chloride, tetraphenylphosphonium bromide, p-tolyltriphenylphosphonium tetra-p-tolylborate ... aromatic phosphonium salts such as tetraphenylborate, tetraphenylphosphonium tetra-p-tolylborate, triphenylethylphosphonium tetraphenylborate, tris(3-methylphenyl)ethylphosphonium tetraphenylborate, tris(2-methoxyphenyl)ethylphosphonium tetraphenylborate, (4-methylphenyl)triphenylphosphonium thiocyanate, tetraphenylphosphonium thiocyanate, and butyltriphenylphosphonium thiocyanate; aromatic phosphine-borane complexes such as triphenylphosphine-triphenylborane; aromatic phosphine-quinone adducts such as triphenylphosphine-p-benzoquinone adduct; aliphatic phosphines such as tributylphosphine, tri-tert-butylphosphine, trioctylphosphine, di-tert-butyl(2-butenyl)phosphine, di-tert-butyl(3-methyl-2-butenyl)phosphine, and tricyclohexylphosphine;Dibutylphenylphosphine, di-tert-butylphenylphosphine, methyldiphenylphosphine, ethyldiphenylphosphine, butyldiphenylphosphine, diphenylcyclohexylphosphine, triphenylphosphine, tri-o-tolylphosphine, tri-m-tolylphosphine, tri-p-tolylphosphine, tris(4-ethylphenyl)phosphine, tris(4-propylphenyl)phosphine, tris(4-isopropylphenyl)phosphine, tris(4-butylphenyl)phosphine, tris(4-tert-butylphenyl)phosphine, tris(2,4-dimethylphenyl)phosphine, tris(2,5-dimethylphenyl)phosphine, tris(2,6-dimethylphenyl)phosphine Examples of aromatic phosphines include tris(3,5-dimethylphenyl)phosphine, tris(2,4,6-trimethylphenyl)phosphine, tris(2,6-dimethyl-4-ethoxyphenyl)phosphine, tris(2-methoxyphenyl)phosphine, tris(4-methoxyphenyl)phosphine, tris(4-ethoxyphenyl)phosphine, tris(4-tert-butoxyphenyl)phosphine, diphenyl-2-pyridylphosphine, 1,2-bis(diphenylphosphino)ethane, 1,3-bis(diphenylphosphino)propane, 1,4-bis(diphenylphosphino)butane, 1,2-bis(diphenylphosphino)acetylene, and 2,2'-bis(diphenylphosphino)diphenyl ether.

[0115] Examples of the urea-based curing accelerator include 1,1-dimethylurea; aliphatic dimethylureas such as 1,1,3-trimethylurea, 3-ethyl-1,1-dimethylurea, 3-cyclohexyl-1,1-dimethylurea, and 3-cyclooctyl-1,1-dimethylurea; 3-phenyl-1,1-dimethylurea, 3-(4-chlorophenyl)-1,1-dimethylurea, 3-(3,4-dichlorophenyl)-1,1-dimethylurea, 3-(3-chloro-4-methylphenyl)-1,1-dimethylurea, 3-(2-methylphenyl)-1,1-dimethylurea, 3-(4-methylphenyl)-1,1-dimethylurea, and 3-(3,4-dimethylphenyl)-1,1-dimethylurea. aromatic dimethylureas such as butylurea, 3-(4-isopropylphenyl)-1,1-dimethylurea, 3-(4-methoxyphenyl)-1,1-dimethylurea, 3-(4-nitrophenyl)-1,1-dimethylurea, 3-[4-(4-methoxyphenoxy)phenyl]-1,1-dimethylurea, 3-[4-(4-chlorophenoxy)phenyl]-1,1-dimethylurea, 3-[3-(trifluoromethyl)phenyl]-1,1-dimethylurea, N,N-(1,4-phenylene)bis(N',N'-dimethylurea), and N,N-(4-methyl-1,3-phenylene)bis(N',N'-dimethylurea) [toluene bisdimethylurea].

[0116] Examples of the guanidine curing accelerator include dicyandiamide, 1-methylguanidine, 1-ethylguanidine, 1-cyclohexylguanidine, 1-phenylguanidine, 1-(o-tolyl)guanidine, dimethylguanidine, diphenylguanidine, trimethylguanidine, tetramethylguanidine, pentamethylguanidine, 1,5,7-triazabicyclo[4.4.0]dec-5-ene, 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene, 1-methylbiguanide, 1-ethylbiguanide, 1-n-butylbiguanide, 1-n-octadecylbiguanide, 1,1-dimethylbiguanide, 1,1-diethylbiguanide, 1-cyclohexylbiguanide, 1-allylbiguanide, 1-phenylbiguanide, and 1-(o-tolyl)biguanide.

[0117] Examples of the imidazole-based curing accelerator include 2-methylimidazole, 2-undecylimidazole, 2-heptadecylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 1,2-dimethylimidazole, 2-ethyl-4-methylimidazole, 2-phenylimidazole, 2-phenyl-4-methylimidazole, 1-benzyl-2-methylimidazole, and 1-benzyl-2-methylimidazole. Phenylimidazole, 1-cyanoethyl-2-methylimidazole, 1-cyanoethyl-2-undecylimidazole, 1-cyanoethyl-2-ethyl-4-methylimidazole, 1-cyanoethyl-2-phenylimidazole, 1-cyanoethyl-2-undecylimidazolium trimellitate, 1-cyanoethyl-2-phenylimidazolium trimellitate, 2,4-diamino-6-[2'-methylimidazolyl -(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-undecylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-ethyl-4'-methylimidazolyl-(1')]-ethyl-s-triazine, 2,4-diamino-6-[2'-methylimidazolyl-(1')]-ethyl-s-triazine isocyanuric acid adduct, 2-phenylimidazole isocyanuric acid adduct imidazole compounds such as 2-phenyl-4,5-dihydroxymethylimidazole, 2-phenyl-4-methyl-5-hydroxymethylimidazole, 2,3-dihydro-1H-pyrrolo[1,2-a]benzimidazole, 1-dodecyl-2-methyl-3-benzylimidazolium chloride, 2-methylimidazoline, and 2-phenylimidazoline, as well as adducts of imidazole compounds and epoxy resins.

[0118] As the imidazole-based curing accelerator, commercially available products may be used, for example, "1B2PZ", "2MZA-PW", "2PHZ-PW", and "C11Z-A" manufactured by Shikoku Chemical Industry Co., Ltd., and "P200-H50" manufactured by Mitsubishi Chemical Corporation.

[0119] Examples of metal-based curing accelerators include organometallic complexes or organometallic salts of metals such as cobalt, copper, zinc, iron, nickel, manganese, and tin. Specific examples of organometallic complexes include organocobalt complexes such as cobalt(II) acetylacetonate and cobalt(4) acetylacetonate, organocopper complexes such as copper(II) acetylacetonate, organozinc complexes such as zinc(II) acetylacetonate, organoiron complexes such as iron(4) acetylacetonate, organonickel complexes such as nickel(II) acetylacetonate, and organomanganese complexes such as manganese(II) acetylacetonate. Examples of organometallic salts include zinc octylate, tin octylate, zinc naphthenate, cobalt naphthenate, tin stearate, and zinc stearate.

[0120] Examples of the amine curing accelerator include trialkylamines such as triethylamine and tributylamine, 4-dimethylaminopyridine, benzyldimethylamine, 2,4,6-tris(dimethylaminomethyl)phenol, and 1,8-diazabicyclo(5,4,0)-undecene.

[0121] As the amine-based curing accelerator, a commercially available product may be used, for example, "MY-25" manufactured by Ajinomoto Fine-Techno Co., Ltd.

[0122] The content of the (F) curing accelerator in the resin composition is not particularly limited, but when the total of the components other than the (B) organic solvent in the resin composition (non-volatile components) is taken as 100 mass%, the upper limit is preferably 5 mass% or less, more preferably 1 mass% or less, even more preferably 0.5 mass% or less, and particularly preferably 0.2 mass% or less, and the lower limit can be, for example, 0 mass% or more, 0.001 mass% or more, 0.01 mass% or more, 0.05 mass% or more, etc.

[0123] <(G) Other Additives> The resin composition of the present invention may further contain any additive. Examples of such additives include rubber particles; radical polymerizable compounds having ethylenically unsaturated bonds; radical polymerization initiators such as peroxide radical polymerization initiators and azo radical polymerization initiators; thermosetting resins other than epoxy resins such as epoxy acrylate resins, urethane acrylate resins, urethane resins, cyanate resins, benzoxazine resins, unsaturated polyester resins, phenolic resins, melamine resins, and silicone resins; organic metal compounds such as organic copper compounds, organic zinc compounds, and organic cobalt compounds; colorants such as phthalocyanine blue, phthalocyanine green, iodine green, diazo yellow, crystal violet, titanium oxide, and carbon black; polymerization inhibitors such as hydroquinone, catechol, pyrogallol, and phenothiazine; leveling agents such as silicone leveling agents and acrylic polymer leveling agents; thickeners such as bentone and montmorillonite; silicone defoamers, acrylic defoamers, fluorine defoamers, and vinyl resins. defoaming agents such as benzotriazole-based defoaming agents; ultraviolet absorbers such as benzotriazole-based ultraviolet absorbers; adhesion improvers such as urea silanes; adhesion promoters such as triazole-based adhesion promoters, tetrazole-based adhesion promoters, and triazine-based adhesion promoters; antioxidants such as hindered phenol-based antioxidants; fluorescent brighteners such as stilbene derivatives; surfactants such as fluorine-based surfactants and silicone-based surfactants; phosphorus-based flame retardants (e.g., phosphate ester compounds, phosphazene compounds, phosphinic acid compounds, red phosphorus ), nitrogen-based flame retardants (e.g., melamine sulfate), halogen-based flame retardants, inorganic flame retardants (e.g., antimony trioxide), and other flame retardants; dispersants such as phosphate ester-based dispersants, polyoxyalkylene-based dispersants, acetylene-based dispersants, silicone-based dispersants, anionic dispersants, and cationic dispersants; and stabilizers such as borate-based stabilizers, titanate-based stabilizers, aluminate-based stabilizers, zirconate-based stabilizers, isocyanate-based stabilizers, carboxylic acid-based stabilizers, and carboxylic anhydride-based stabilizers. (G) Other additives may be used alone or in combination of two or more at any ratio. The content of (G) other additives can be appropriately determined by those skilled in the art.

[0124] The content of the radical polymerizable compound is, for example, 0% by mass to 30% by mass, preferably 0% by mass to 10% by mass, more preferably 0% by mass to 5% by mass, even more preferably 0% by mass to 2% by mass, still more preferably 0% by mass to 1% by mass, and particularly preferably 0% by mass to 0.1% by mass, when the total of components other than the (B) organic solvent in the resin composition (non-volatile components) is taken as 100% by mass.

[0125] <Method of producing resin composition> The resin composition of the present invention can be produced by appropriately mixing the above-described components and, if necessary, kneading or stirring the mixture with a kneading means such as a triple roll mill, a ball mill, a bead mill, or a sand mill, or a stirring means such as a super mixer, a planetary mixer, or a high-speed rotary mixer.

[0126] <Form of Resin Composition> The resin composition of the present invention has a viscosity, measured using an E-type viscometer at 25°C and 50 rpm, of 3 mPa·s or more, preferably 5 mPa·s or more, more preferably 10 mPa·s or more, even more preferably 30 mPa·s or more, and particularly preferably 50 mPa·s or more, and the upper limit is 5,000 mPa·s or less, preferably 4,000 mPa·s or less, more preferably 3,000 mPa·s or less, even more preferably 2,000 mPa·s or less, even more preferably 1,500 mPa·s or less, still more preferably 1,000 mPa·s or less, and particularly preferably 800 mPa·s or less.

[0127] The resin composition of the present invention has a viscosity, measured using an E-type viscometer at 25°C and 5 rpm, of preferably 3 mPa·s or more, more preferably 5 mPa·s or more, even more preferably 10 mPa·s or more, even more preferably 30 mPa·s or more, and particularly preferably 50 mPa·s or more, and the upper limit is preferably 5,000 mPa·s or less, more preferably 4,000 mPa·s or less, even more preferably 3,000 mPa·s or less, even more preferably 2,000 mPa·s or less, still more preferably 1,500 mPa·s or less, and particularly preferably 1,000 mPa·s or less.

[0128] The resin composition of the present invention has a thixotropy ratio, calculated by dividing the viscosity measured using an E-type viscometer at 25°C and 5 rpm by the viscosity measured using an E-type viscometer at 25°C and 50 rpm, of, for example, 1.00 or more, and the upper limit is preferably 3.00 or less, more preferably 2.00 or less, even more preferably 1.50 or less, still more preferably 1.30 or less, still more preferably 1.20 or less, particularly preferably 1.15 or less, and particularly preferably 1.12 or less.

[0129] <Characteristics of resin composition> The resin composition of the present invention comprises (A) an epoxy resin, (B) an organic solvent, and (C) an inorganic filler, and the content of the organic solvent having a boiling point of less than 100°C in the (B) component is 5% to 60% by mass when the total (B) component is taken as 100% by mass, the content of the aromatic solvent in the (B) component is 35% by mass or more when the total (B) component is taken as 100% by mass, and the viscosity measured by an E-type viscometer under conditions of 25°C and 50 rpm is 3 mPa·s to 5,000 mPa·s. Such a resin composition is unlikely to cause resin separation. Furthermore, by using such a resin composition, nozzle clogging due to drying of the nozzle can be suppressed, while excellent drying properties after application can be achieved. Furthermore, such a resin composition can be excellent in thin film formability (for example, coating film formability with a thickness of 50 μm or less). Furthermore, such a resin composition can suppress cissing defects after application.

[0130] In one embodiment, the cured product (insulating layer) obtained by curing the resin composition of the present invention may be characterized by excellent insulation. The insulation resistance value of the cured product (insulating layer) obtained by curing the resin composition, measured as in Test Example 5 below, is preferably 1.0×10 4 Ω or more, preferably 1.0×10 6 Ω or more, and even more preferably 1.0×10 7 Ω or more, and even more preferably 1.0×10 9 Ω or more, particularly preferably 1.0×10 10 More than Ω.

[0131] <Applications of resin composition> The resin composition of the present invention can be suitably used as a resin composition for forming an insulating layer (particularly, an (interlayer) insulating layer of a printed wiring board) by applying the resin composition to a substrate by a roll coating method, a spray coating method, a spin coating method, a bar coating method, a slit coating method, a curtain coating method, or a dipping method to form a coating film, and then heat-curing the coating film, preferably a resin composition for forming an insulating layer (particularly, an (interlayer) insulating layer of a printed wiring board) by applying the resin composition to a substrate by a slit coating method to form a coating film, and then heat-curing the coating film, particularly preferably a resin composition for forming a thin insulating layer (thickness 50 μm or less) by applying the resin composition to a substrate by a slit coating method to form a coating film, and then heat-curing the coating film, particularly preferably a resin composition for forming a thin insulating layer (particularly, an (interlayer) insulating layer of a printed wiring board ...thickness 50 μm or less) by applying the resin composition to a substrate by a slit coating method to form a coating film, and then heat-curing the coating film,

[0132] <Printed wiring board> The printed wiring board of the present invention comprises an insulating layer obtained by curing the resin composition of the present invention.

[0133] The printed wiring board can be produced, for example, by using the resin composition of the present invention, by a method including the following steps (1) to (3). (1) A step of applying a resin composition onto a substrate to form a coating film (2) Drying the coating (3) The coating is thermally cured to form an insulating layer.

[0134] Step (1) is a step of applying a resin composition onto a substrate to form a coating film.

[0135] The "substrate" used in step (1) is a member that will be the substrate of the printed wiring board, and examples thereof include a glass epoxy substrate, a metal substrate, a polyester substrate, a polyimide substrate, a BT resin substrate, a thermosetting polyphenylene ether substrate, and a glass substrate. The substrate may have a conductor layer on one or both sides, and the conductor layer may be patterned. An inner layer substrate having a conductor layer (circuit) formed on one or both sides of the substrate may be called an "inner layer circuit substrate". In addition, an intermediate product on which an insulating layer and / or a conductor layer is to be further formed during the manufacture of a printed wiring board is also included in the "substrate" of the present invention. When the printed wiring board is a circuit board with built-in components, an inner layer substrate with built-in components may be used.

[0136] The resin composition can be applied onto a substrate by, for example, roll coating, spray coating, spin coating, bar coating, slit coating, curtain coating, or dipping. Among these, the resin composition of the present invention is preferably applied by slit coating.

[0137] The thickness of the coating film formed by step (1) is preferably 200 μm or less, more preferably 100 μm or less, even more preferably 50 μm or less, even more preferably 40 μm or less, and particularly preferably 30 μm or less, from the viewpoint of thin film formation. The resin composition of the present invention is particularly useful in forming a thin film of 50 μm or less by a slit coating method, in which nozzle clogging due to nozzle drying is a significant problem. The lower limit of the thickness of the coating film is not particularly limited, and can be, for example, 0.1 μm or more, 0.5 μm or more, 1 μm or more, 3 μm or more, 5 μm or more, 10 μm or more, etc.

[0138] Step (2) is a step of drying the coating film. The drying conditions for the resin composition are not particularly limited, and the conditions usually adopted for forming an insulating layer for a printed wiring board may be used.

[0139] The coating film in step (2) can be dried, for example, by vacuuming, reducing pressure, heating, blowing hot air, or a combination of these, and is preferably dried by vacuum drying (including reduced pressure drying) and / or heating. By drying the coating film in step (2), the content of the organic solvent in the resin composition is preferably set to 10 mass% or less, more preferably 5 mass% or less.

[0140] In the step (2), when the coating film is vacuum-dried, the air pressure is preferably not more than 500 Pa, and more preferably not more than 200 Pa. The vacuum drying time is not particularly limited, but is preferably 30 seconds to 30 minutes, and more preferably 30 seconds to 10 minutes.

[0141] In step (2), when the coating film is dried by heating, the heating and drying temperature is preferably 50° C. or more and less than 200° C., more preferably 50° C. or more and less than 150° C., even more preferably 50° C. or more and less than 140° C., still more preferably 70° C. or more and less than 130° C., and particularly preferably 80° C. or more and less than 120° C. The heating and drying time for maintaining the above heating and drying temperature is preferably 1 minute to 30 minutes, more preferably 1 minute to 10 minutes, and even more preferably 1 minute to 5 minutes.

[0142] In the drying of the coating film in step (2), it is particularly preferable to carry out vacuum drying before drying by heating. When drying by heating, the viscosity of the coating film decreases as the temperature of the coating film increases, and the coating film may flow, causing unevenness or cissing, but in the case of vacuum drying, there is no heating, and instead the temperature of the coating film decreases and the viscosity increases due to the heat of vaporization, so that the coating film can be prevented from flowing.

[0143] Step (3) is a step of thermally curing the coating film to form an insulating layer. The thermal curing conditions of the resin composition are not particularly limited, and conditions usually adopted for forming an insulating layer of a printed wiring board may be used.

[0144] The heat curing conditions of the resin composition vary depending on the types of components contained in the resin composition, but in one embodiment, the curing temperature is preferably 150° C. or higher and 240° C. or lower, more preferably 160° C. or higher and 220° C. or lower, and even more preferably 170° C. or higher and 210° C. or lower. The curing time for maintaining the above curing temperature can be preferably 30 minutes to 300 minutes, more preferably 60 minutes to 240 minutes, and even more preferably 90 minutes to 180 minutes.

[0145] The thickness of the insulating layer formed in step (3) is preferably 200 μm or less, more preferably 100 μm or less, even more preferably 50 μm or less, even more preferably 40 μm or less, and particularly preferably 30 μm or less. The lower limit of the thickness of the insulating layer is not particularly limited, and may be, for example, 0.1 μm or more, 0.5 μm or more, 1 μm or more, 3 μm or more, 5 μm or more, 10 μm or more, etc.

[0146] In manufacturing a printed wiring board, in addition to the above steps (1) to (3), a step (4) of drilling holes in the insulating layer, a step (5) of roughening the insulating layer, and a step (6) of forming a conductor layer may be further carried out. These steps (4) to (6) may be carried out according to various methods used in manufacturing printed wiring boards and known to those skilled in the art. Furthermore, if necessary, the formation of the insulating layer and the conductor layer in steps (1) to (6) may be repeated to form a multilayer wiring board.

[0147] Step (4) is a step of drilling holes in the insulating layer, which allows holes such as via holes and through holes to be formed in the insulating layer. Step (4) may be performed using, for example, a drill, a laser, plasma, or the like, depending on the composition of the resin composition used to form the insulating layer. The dimensions and shape of the holes may be appropriately determined depending on the design of the printed wiring board.

[0148] Step (5) is a step of roughening the insulating layer. Usually, smears are also removed in this step (5). The procedure and conditions of the roughening treatment are not particularly limited, and known procedures and conditions that are usually used when forming an insulating layer of a printed wiring board can be adopted. For example, the insulating layer can be roughened by carrying out a swelling treatment with a swelling liquid, a roughening treatment with an oxidizing agent, and a neutralization treatment with a neutralizing liquid in this order.

[0149] The swelling liquid used in the roughening treatment is not particularly limited, but includes an alkaline solution, a surfactant solution, etc., and is preferably an alkaline solution, and more preferably a sodium hydroxide solution or a potassium hydroxide solution. Examples of commercially available swelling liquids include "Swelling Dip Securigans P" and "Swelling Dip Securigans SBU" manufactured by Atotech Japan. The swelling treatment using the swelling liquid is not particularly limited, but can be performed by immersing the insulating layer in a swelling liquid at 30°C to 90°C for 1 to 20 minutes, for example. From the viewpoint of suppressing the swelling of the resin of the insulating layer to an appropriate level, it is preferable to immerse the insulating layer in a swelling liquid at 40°C to 80°C for 5 to 15 minutes.

[0150] The oxidizing agent used in the roughening treatment is not particularly limited, but examples thereof include an alkaline permanganate solution in which potassium permanganate or sodium permanganate is dissolved in an aqueous solution of sodium hydroxide. The roughening treatment using an oxidizing agent such as an alkaline permanganate solution is preferably performed by immersing the insulating layer in an oxidizing agent solution heated to 60°C to 100°C for 10 minutes to 30 minutes. The concentration of permanganate in the alkaline permanganate solution is preferably 5% by mass to 10% by mass. Examples of commercially available oxidizing agents include alkaline permanganate solutions such as "Concentrate Compact CP" and "Dosing Solution Securigans P" manufactured by Atotech Japan.

[0151] The neutralizing solution used in the roughening treatment is preferably an acidic aqueous solution, and a commercially available product such as "Reduction Solution Securigant P" manufactured by Atotech Japan can be mentioned.

[0152] The treatment with the neutralizing solution can be carried out by immersing the surface that has been roughened with an oxidizing agent in a neutralizing solution at 30° C. to 80° C. for 5 to 30 minutes. From the viewpoint of workability, etc., a method in which the object that has been roughened with an oxidizing agent is immersed in a neutralizing solution at 40° C. to 70° C. for 5 to 20 minutes is preferred.

[0153] In one embodiment, the arithmetic mean roughness (Ra) of the insulating layer surface after the roughening treatment is not particularly limited, but is preferably 500 nm or less, more preferably 400 nm or less, and even more preferably 300 nm or less. The lower limit is not particularly limited, and may be, for example, 1 nm or more, 2 nm or more, etc. The root mean square roughness (Rq) of the insulating layer surface after the roughening treatment is preferably 500 nm or less, more preferably 400 nm or less, and even more preferably 300 nm or less. The lower limit is not particularly limited, and may be, for example, 1 nm or more, 2 nm or more, etc. The arithmetic mean roughness (Ra) and root mean square roughness (Rq) of the insulating layer surface can be measured using a non-contact surface roughness meter.

[0154] Step (6) is a step of forming a conductor layer, and the conductor layer is formed on the insulating layer. The conductor material used for the conductor layer is not particularly limited. In a preferred embodiment, the conductor layer contains one or more metals selected from the group consisting of gold, platinum, palladium, silver, copper, aluminum, cobalt, chromium, zinc, nickel, titanium, tungsten, iron, tin and indium. The conductor layer may be a single metal layer or an alloy layer, and examples of the alloy layer include layers formed from alloys of two or more metals selected from the above group (e.g., nickel-chromium alloy, copper-nickel alloy and copper-titanium alloy). Among these, from the viewpoints of versatility in forming the conductor layer, cost, ease of patterning, and the like, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy, a copper-nickel alloy, or a copper-titanium alloy is preferred, a single metal layer of chromium, nickel, titanium, aluminum, zinc, gold, palladium, silver, or copper, or an alloy layer of a nickel-chromium alloy is more preferred, and a single metal layer of copper is even more preferred.

[0155] The conductor layer may be a single-layer structure or a multi-layer structure in which two or more single metal layers or alloy layers made of different kinds of metals or alloys are laminated. When the conductor layer has a multi-layer structure, the layer in contact with the insulating layer is preferably a single metal layer of chromium, zinc or titanium, or an alloy layer of a nickel-chromium alloy.

[0156] The thickness of the conductor layer depends on the desired design of the printed wiring board, but is generally 3 μm to 35 μm, preferably 5 μm to 30 μm.

[0157] In one embodiment, the conductor layer may be formed by plating. For example, a conductor layer having a desired wiring pattern can be formed by plating the surface of the insulating layer by a conventionally known technique such as a semi-additive method or a full-additive method, and from the viewpoint of ease of production, it is preferable to form the conductor layer by the semi-additive method. An example of forming the conductor layer by the semi-additive method will be described below.

[0158] First, a plating seed layer is formed on the surface of an insulating layer by electroless plating. Next, a mask pattern is formed on the formed plating seed layer to expose a part of the plating seed layer corresponding to a desired wiring pattern. After a metal layer is formed on the exposed plating seed layer by electrolytic plating, the mask pattern is removed. Thereafter, unnecessary plating seed layer is removed by etching or the like to form a conductor layer having a desired wiring pattern.

[0159] <Semiconductor device> The printed wiring board described above can be used in a semiconductor device including a printed wiring board.

[0160] Examples of the semiconductor device include various semiconductor devices used in electric appliances (eg, computers, mobile phones, digital cameras, televisions, etc.) and vehicles (eg, motorcycles, automobiles, trains, ships, aircraft, etc.). EXAMPLES

[0161] The present invention will be specifically described below with reference to examples. The present invention is not limited to these examples. In the following, "parts" and "%" representing amounts mean "parts by mass" and "% by mass", respectively, unless otherwise specified. Unless otherwise specified, the temperature and pressure conditions are room temperature (25°C) and normal pressure (1 atm), respectively.

[0162] <Example 1> Biphenyl epoxy resin (Nippon Kayaku Co., Ltd. "NC-3000L") 43 parts, bisphenol epoxy resin (Nippon Steel Chemical & Material Co., Ltd. "ZX1059") 28 parts, aminotriazine skeleton cresol novolac resin (DIC Corp. "LA-3018-50P", 50% solids PGM (propylene glycol monomethyl ether (also known as 1-methoxy-2-propanol)) solution) 10 parts, active ester curing agent (DIC Corp. "HPC-8000-65T", 65% solids toluene solution) 45 parts, phenoxy resin (Mitsubishi Chemical Corp. "YX7553BH30", 30% solids Anone (cyclohexanone ) / MEK (methyl ethyl ketone) (1:1) solution), 26 parts of spherical silica (100 parts of "SOC2" manufactured by Admatechs Co., Ltd., surface-treated with 0.6 parts of an aminosilane coupling agent ("KBM-573" manufactured by Shin-Etsu Chemical Co., Ltd., N-phenyl-3-aminopropyltrimethoxysilane), average particle size 0.5 μm, 350 parts of 4-dimethylaminopyridine ("DMAP" manufactured by Tokyo Chemical Industry Co., Ltd.), 0.5 parts of MEK (methyl ethyl ketone), 50 parts of MEK (methyl ethyl ketone), and 360 parts of an aromatic high boiling point solvent ("IPZOL 150" manufactured by Idemitsu Kosan Co., Ltd., initial boiling point 184 ° C, dry point 205 ° C) were mixed and stirred at room temperature until a uniform solution was obtained, to obtain a varnish-like resin composition.

[0163] <Example 2> A varnish-like resin composition was obtained in the same manner as in Example 1, except that the amount of the aromatic high-boiling point solvent (Ipzol 150, manufactured by Idemitsu Kosan Co., Ltd.) used was changed from 360 parts to 160 parts.

[0164] <Example 3> A varnish-like resin composition was obtained in the same manner as in Example 1, except that the amount of the aromatic high-boiling point solvent (Ipzol 150, manufactured by Idemitsu Kosan Co., Ltd.) used was changed from 360 parts to 25 parts.

[0165] <Example 4> A varnish-like resin composition was obtained in the same manner as in Example 1, except that 43 parts of a dicyclopentadiene-type epoxy resin ("HP7200" manufactured by DIC Corporation) was used instead of 43 parts of a biphenyl-type epoxy resin ("NC-3000L" manufactured by Nippon Kayaku Co., Ltd.) and the amount of an aromatic high-boiling point solvent ("IPZOL 150" manufactured by Idemitsu Kosan Co., Ltd.) used was changed from 360 parts to 160 parts.

[0166] <Example 5> A varnish-like resin composition was obtained in the same manner as in Example 1, except that 20 parts of MEK (methyl ethyl ketone) was additionally used and the amount of aromatic high-boiling point solvent (Idemitsu Kosan's "IPZOL 150") used was changed from 360 parts to 50 parts.

[0167] <Example 6> A varnish-like resin composition was obtained in the same manner as in Example 1, except that 40 parts of MEK (methyl ethyl ketone) was additionally used and the amount of aromatic high-boiling point solvent (Idemitsu Kosan's "IPZOL 150") used was changed from 360 parts to 50 parts.

[0168] <Example 7> A varnish-like resin composition was obtained in the same manner as in Example 1, except that 45 parts of an active ester-based curing agent ("HPC-8000-65T" manufactured by DIC Corporation, a toluene solution with a solid content of 65% by mass) was not used.

[0169] <Example 8> A varnish-like resin composition was obtained in the same manner as in Example 1, except that the amount of aromatic high-boiling point solvent (Idemitsu Kosan's "IPZOL 150") used was changed from 360 parts to 160 parts, and 45 parts of active ester curing agent (DIC's "HPC-8000-65T", a toluene solution with a solid content of 65% by mass) was not used.

[0170] <Example 9> A varnish-like resin composition was obtained in the same manner as in Example 1, except that the amount of aromatic high-boiling point solvent (Idemitsu Kosan's "IPZOL 150") used was changed from 360 parts to 40 parts, and 45 parts of active ester curing agent (DIC's "HPC-8000-65T", a toluene solution with a solid content of 65% by mass) was not used.

[0171] <Comparative Example 1> A varnish-like resin composition was obtained in the same manner as in Example 1, except that 50 parts of MEK (methyl ethyl ketone) was additionally used and the amount of aromatic high-boiling point solvent (Idemitsu Kosan Co., Ltd.'s "IPZOL 150") used was changed from 360 parts to 30 parts.

[0172] <Comparative Example 2> A varnish-like resin composition was obtained in the same manner as in Example 1, except that 160 parts of Anone (cyclohexanone) was additionally used and 360 parts of an aromatic high-boiling point solvent (Idemitsu Kosan Co., Ltd.'s "IPZOL 150") was not used.

[0173] <Comparative Example 3> A varnish-like resin composition was obtained in the same manner as in Example 1, except that 160 parts of NMP (N-methyl-2-pyrrolidone) was additionally used and 360 parts of an aromatic high-boiling point solvent (Idemitsu Kosan Co., Ltd.'s "IPZOL 150") was not used.

[0174] <Comparative Example 4> A varnish-like resin composition was obtained in the same manner as in Example 1, except that 160 parts of GBL (γ-butyrolactone) was additionally used and 360 parts of an aromatic high-boiling point solvent (Idemitsu Kosan Co., Ltd.'s "IPZOL 150") was not used.

[0175] <Comparative Example 5> A varnish-like resin composition was obtained in the same manner as in Example 1, except that the amount of the aromatic high-boiling point solvent (Ipzol 150, manufactured by Idemitsu Kosan Co., Ltd.) used was changed from 360 parts to 500 parts.

[0176] <Comparative Example 6> A varnish-like resin composition was obtained in the same manner as in Example 1, except that the amount of aromatic high-boiling point solvent (Idemitsu Kosan's "IPZOL 150") used was changed from 360 parts to 25 parts, and 50 parts of MEK (methyl ethyl ketone) was not used.

[0177] <Test Example 1: Evaluation of suppression of nozzle clogging due to nozzle drying> The varnish-like resin composition obtained in the above Examples or Comparative Examples was put into a slit coater (Kondo Co., Ltd.), and slit-coated one glass plate to a film thickness of 25 μm. After slit-coating, the plate was left to stand for 20 minutes, and then slit-coated again. When a uniform coating film was formed, it was evaluated as "○", and when a uniform coating film could not be formed due to nozzle clogging, it was evaluated as "×".

[0178] <Test Example 2: Evaluation of drying properties after application> The varnish-like resin composition obtained in the above Examples or Comparative Examples was put into a slit coater (Kondo Co., Ltd.), and one glass plate was slit-coated to a film thickness of 25 μm. The glass plate on which the coating film was formed by slit coating was vacuum-dried for 1 minute, then dried on a hot plate at 100°C for 3 minutes, and a PET film was placed on the coating film and left at room temperature for 30 minutes. After leaving it, the coating film and the PET film were not in contact with each other and were evaluated as "○", and those that were in contact were evaluated as "×".

[0179] <Test Example 3: Evaluation of repelling defects after application> The varnish-like resin composition obtained in the above Examples or Comparative Examples was put into a slit coater (manufactured by Kondo Co., Ltd.), and slit-coated one glass plate to a film thickness of 25 μm. The glass plate on which the coating film was formed by slit coating was vacuum-dried for 1 minute, then dried on a hot plate at 100°C for 3 minutes, and further heated in an oven at 180°C for 40 minutes. When the thickness of the entire substrate obtained was measured, a thickness difference of less than 5 μm was evaluated as "○", and a thickness difference of 5 μm or more was evaluated as "×". Here, the thickness difference includes the variation between the coating start point, midpoint, and end point (X direction), and the variation between the center of the left and right of the coater (Y direction), and both were measured and evaluated.

[0180] <Test Example 4: Evaluation of thin film formability> In the measurement of the thickness of the entire substrate performed in Test Example 3, the average film thickness was evaluated as "good" if it was 25 μm±2 μm, and was evaluated as "poor" if it was not.

[0181] <Test Example 5: Insulation Resistance Test> The varnish-like resin composition obtained in the above Examples or Comparative Examples was put into a slit coater (Kondo Co., Ltd.), slit-coated onto a copper-clad laminate to a film thickness of 25 μm, and the obtained sample was vacuum-dried for 1 minute, and then dried on a hot plate at 100°C for 3 minutes. Copper foil was placed on the coating of the dried sample, and the copper foil was laminated using a vacuum laminator, and then heated in an oven at 180°C for 40 minutes, and then heated in an oven at 200°C for 120 minutes to completely cure the coating. A voltage of 5V was applied between the copper-clad laminate and the copper foil of the obtained sample to measure the insulation resistance value. The insulation resistance value was 1.0×10 7 Ω or more is marked as "〇", 1.0×10 7 Those with a value of less than Ω were evaluated as "x".

[0182] <Test Example 6: Measurement of viscosity and calculation of thixotropy ratio> The viscosity of the varnish-like resin composition was measured for 2 minutes using an E-type viscometer (RE80 type viscometer manufactured by Toki Sangyo Co., Ltd.) under the conditions of a measurement temperature of 25°C, a rotor of 1.34°×R24, an amount of the varnish-like resin composition of 1.2 ml, and rotation speeds of 5 rpm and 50 rpm. Furthermore, the thixotropic ratio was calculated by dividing the viscosity measured at 5 rpm by the viscosity measured at 50 rpm.

[0183] <Test Example 7: Evaluation of resin separation failure> The varnish-like resin composition obtained in the above Examples or Comparative Examples was stored in an environment of -40°C for one week, and then allowed to stand in a room temperature atmosphere of 25°C until the temperature of the resin composition reached 25°C. A preparation of the resin composition at 25°C was made using a slide glass and a cover glass, and observed under an optical microscope to confirm the presence or absence of poor separation of the resin.

[0184] The occurrence of resin separation of about 100 μm was observed at a magnification of 50x, and of about 10 μm at a magnification of 500x. If there was no resin separation in either case, it was judged as "○", and if there was either or both types of resin separation, it was judged as "×".

[0185] <Example 10> The varnish-like resin composition obtained in Example 2 was used, and evaluations were carried out in the same manner as in Test Examples 1 to 7, except that in Test Examples 2 to 5, vacuum drying was not carried out.

[0186] <Example 11> The varnish-like resin composition obtained in Example 2 was used, and evaluations were carried out in the same manner as in Test Examples 1 to 7, except that in Test Examples 1 to 4, the glass plate was changed to a glass epoxy substrate.

[0187] The contents of each component of the resin compositions obtained in the Examples and Comparative Examples, and the measurement results and evaluation results of the Test Examples are shown in Table 1 below.

[0188] [Table 1]

[0189] As shown in Table 1, a resin composition comprising (A) an epoxy resin, (B) an organic solvent, and (C) an inorganic filler, in which the content of organic solvent having a boiling point of less than 100°C in component (B) is 5% by mass to 60% by mass when the total of component (B) is taken as 100% by mass, the content of aromatic solvent in component (B) is 35% by mass or more when the total of component (B) is taken as 100% by mass, and the viscosity measured with an E-type viscometer under conditions of 25°C and 50 rpm is 3 mPa·s to 5,000 mPa·s, can suppress resin separation failure due to low solubility of the resin and nozzle clogging due to nozzle drying, while suppressing cissing failure after application, and has excellent thin film formability.

Claims

1. A resin composition comprising (A) an epoxy resin, (B) an organic solvent, and (C) an inorganic filler, the content of the organic solvent having a boiling point of less than 100° C. in component (B) is 5% by mass to 60% by mass, relative to 100% by mass of the total amount of component (B); the content of the aromatic solvent in the component (B) is 35% by mass or more, relative to 100% by mass of the entire component (B); The viscosity measured with an E-type viscometer at 25°C and 50 rpm is 3 mPa·s to 5,000 mPa·s. A resin composition for forming an insulating layer by applying the resin composition to a substrate by roll coating, spray coating, spin coating, bar coating, slit coating, curtain coating, or dipping to form a coating film, and then thermally curing the coating film.

2. The resin composition according to claim 1, which is a resin composition for forming an insulating layer by applying the resin composition to a substrate by a slit coating method to form a coating film and thermally curing the coating film.

3. The resin composition according to claim 1, wherein the content of the component (C) is 85 mass% or less when the total of the components other than the component (B) in the resin composition is 100 mass%.

4. The resin composition according to claim 1 , wherein the content of the component (C) is 60% by mass or more, relative to 100% by mass of the total of the components other than the component (B) in the resin composition.

5. 2. The resin composition according to claim 1, wherein the content of the aromatic solvent in the component (B) is 85% by mass or less, when the total amount of the component (B) is taken as 100% by mass.

6. The resin composition according to claim 1, wherein the content of the organic solvent having a boiling point of 130° C. or more in the component (B) is 25% by mass to 90% by mass, when the total amount of the component (B) is 100% by mass.

7. The resin composition according to claim 1, wherein the content of the organic solvent having a boiling point of 100° C. or more and less than 130° C. in the component (B) is 1% by mass to 20% by mass, when the total amount of the component (B) is 100% by mass.

8. 2. The resin composition according to claim 1, wherein the content of the organic solvent having a boiling point of 100° C. or more and less than 130° C. in the component (B) is 5% by mass or more, based on 100% by mass of the total of the component (B).

9. 2. The resin composition according to claim 1, wherein the content of the non-aromatic solvent having a boiling point of 130° C. or higher in component (B) is 10% by mass or less, relative to 100% by mass of the total of component (B).

10. 2. The resin composition according to claim 1, wherein the content of the aromatic solvent having a boiling point of 130° C. or higher in the component (B) is 20% by mass or more, relative to 100% by mass of the entire component (B).

11. The resin composition according to claim 1, wherein the content of aromatic solvents having a boiling point of 130° C. or higher in the aromatic solvent is 60% by mass or more, relative to 100% by mass of all aromatic solvents.

12. The component (B) is C 9 Aromatic Hydrocarbons and C 10 The resin composition according to claim 1 , further comprising an aromatic solvent selected from aromatic hydrocarbons.

13. 2. The resin composition according to claim 1, wherein the content of the organic solvent having constituent atoms selected from carbon atoms, oxygen atoms, and hydrogen atoms in the organic solvent (B) is 98 mass% or more, when the total amount of the component (B) is 100 mass%.

14. The resin composition according to claim 1, wherein the content of the component (B) is 15% by mass to 50% by mass, when all components in the resin composition are 100% by mass.

15. The resin composition according to claim 1, wherein the content of the radical polymerizable compound is 0% by mass to 2% by mass, when the total of the components other than the component (B) in the resin composition is 100% by mass.

16. 2. The resin composition according to claim 1, having a viscosity of 50 mPa·s to 1,500 mPa·s as measured with an E-type viscometer at 25° C. and 50 rpm.

17. 2. The resin composition according to claim 1, wherein the thixotropy ratio calculated by dividing the viscosity measured using an E-type viscometer at 25°C and 5 rpm by the viscosity measured using an E-type viscometer at 25°C and 50 rpm is 1.00 to 1.

50.

18. 2. The resin composition according to claim 1, wherein the thixotropy ratio calculated by dividing the viscosity measured using an E-type viscometer at 25°C and 5 rpm by the viscosity measured using an E-type viscometer at 25°C and 50 rpm is 1.00 to 1.

15.

19. A printed wiring board comprising an insulating layer made of a cured product of the resin composition according to any one of claims 1 to 18.

20. A semiconductor device comprising the printed wiring board according to claim 19.

21. (A) an epoxy resin, (B) an organic solvent, and (C) an inorganic filler; the content of the organic solvent having a boiling point of less than 100° C. in component (B) is 5% by mass to 60% by mass, relative to 100% by mass of the total amount of component (B); the content of the aromatic solvent in the component (B) is 35% by mass or more, relative to 100% by mass of the entire component (B); A method for producing a printed wiring board using a resin composition having a viscosity of 3 mPa·s to 5,000 mPa·s as measured with an E-type viscometer at 25°C and 50 rpm, A method for producing a printed wiring board, comprising the following steps (1) to (3): (1) A step of applying the resin composition onto a substrate by a slit coating method to form a coating film. (2) A step of vacuum drying the coating film and / or drying at a temperature of 50° C. or higher and lower than 150° C. (3) A step of thermally curing the coating film at a temperature of 150° C. to 240° C. to form an insulating layer.

Citation Information

Patent Citations

  • Application liquid and carrier material with resin layer

    JP2009057527A

  • Manufacturing method of resin sheet

    JP2017060927A

  • Photocationic curing type epoxy resin composition

    JP2020066643A

  • Resin composition

    JP2024117683A

  • Sealing agent for organic electroluminescence display element

    WO2015178186A1